Ultrastructural characterization of the egg chorion and reproductive anatomy of potato tuber moth, Phthorimaea operculella (Zeller) (Lepidoptera: Gelechiidae) - Pranita Roy; Suresh R. Jambagi; K. Logeswaran; Doddachowdappa Sagar; M. Mohan; G. Mahendiran; D. Nandhini (Tissue and Cell, 2027)

Computational Analysis of Peptide Binding on Dengue-Associated Host Proteins POLR2A and Elongin C: Network Pharmacology, Molecular Docking, and Dynamics Simulation Insights - S. Mohammed Zaidh; M. H. Mohamed Asrarullah; Kathiravan Muthukumaradoss; N. Parvin; N. Irfan; Mohan Maruga Raja Muthu Kumaradoss (Journal of Pharmaceutical Innovation, 2027)

Recent advances in pectin-based films for sustainable intelligent packaging applications in animal-derived foods - C.S. Krishna Murthy; Rajesh Kumar; T. Jagan Mohan Rao; Amarendar Reddy M (Food Control, 2026)

EBV-informed multi-omics target prioritization and structure-based drug repurposing reveal potential therapeutic strategies for multiple sclerosis - Nevil M. Lal; Harshit Sajal; Aswin Mohan; Asna R.; Fadiya Fathima; Rajesh Raju; Anuroopa G. Nadh (Functional & Integrative Genomics, 2026)

Wastewater antibody signatures reflect SARS-CoV-2 infection and immunization patterns in the population - Dhammika Leshan Wannigama; Mohan Amarasiri; Phatthranit Phattharapornjaroen; Cameron Hurst; Charin Modchang; John Giles; Jillian Gauld; Tanakorn Chantanasaro; Kazuhiko Miyanaga; Longzhu Cui; Stefan Fernandez; Hirotake Mori; et al. (Water Research, 2026)

An analysis of the flow pattern of EICC during the positive Indian Ocean dipole events - Vishwanath Boopathi; Vidya S. Mohan; M. Jishad; Jaya Kumar Seelam (Regional Studies in Marine Science, 2026)

Rice immunity against Asian rice gall midge: from resistance genes to precision breeding - G. Rakesh; B. Vidhyadhar; Y. Chandra Mohan; Yadla Hari; R. Shravan Kumar; P. Gonya Naik; B. Manju Bhargavi; G. Anil kumar; M. Saicharan; Ramya Rathod (Cereal Research Communications, 2026)

Normalization of candidate reference genes for precise qRT-PCR quantification in Maruca vitrata F. (Lepidoptera: Crambidae) under multiple biotic and abiotic stress regimes - C. R. Chandana; Sushila Nadagouda; Muthugounder Mohan; A. Sunny Rao; Basavaraj S. Kalmath; Shivaleela Gouda; Jayaprakash M. Nidagundi; Saroja Narsinga Rao (International Journal of Tropical Insect Science, 2026)

Impact of advanced cloud microphysics schemes for the Kerala flood events in 2018 and 2019 using the NCMRWF regional model - Rose Raphel; A. Jayakumar; T.J. Anurose; Saji Mohandas; Greeshma M. Mohan; M. Sandhya; Anumeha Dube; Donali Gogoi; V.S. Prasad; Claudio Sanchez (Atmospheric Research, 2026)

Preliminary Investigation of Phosphorus-Use Efficiency in Mungbean (Vigna radiata): A Comparative RNA-Seq Study - Deepali Kothari; Muraleedhar S. Aski; S. Premakumar; Bidwan Rath; Nirmala Pargaien; Lalit Mohan Tewari; Shouvik Das; Gyan Prakash Mishra; Gyanendra Singh; Prachi Shripatrao Yadav; Ya-Ping Lin; Roland Schafleitner; et al. (Indian Journal of Genetics and Plant Breeding, 2026)

Yoga-Based Therapy Versus Cognitive Behavioural Therapy for Chronic Insomnia Along with Pharmacotherapy: A Randomised Equivalence Trial - Gaurav Saurabh Sharma; Ravi Gupta; Poorvi Kulshreshtha; Puneet Dhamija; Latika Mohan; M. Raghvendra Rao (Sleep and Vigilance, 2026)

Molecular and functional analysis of RNAi machinery genes in a neuropteran insect predator, Chrysoperla zastrowi sillemi - V. S. Chinnu; M. Mohan; R. Manjunatha; P. J. Aneesha; Suresh R. Jambagi (BioControl, 2026)

Lightweight Composite Alternatives to Sandbags: Mechanics of Ballistic Impact, Energy Absorption, and Fragmentation Behavior - Saleemsab Doddamani; Satyabodh M. Kulkarni; Sharnappa Joladarashi; Ashish Kumar Gurjar; Mohan Kumar TS (Next Research, 2026)

Linking environmental DNA and acoustic telemetry to monitor Striped Bass (Morone saxatilis) in an estuarine ecosystem - Kade O. Tyrrell; Emily R. Lancaster; Benjamin P. Gowell; Josephine M. Pikowski; Charles E. Tilburg; John A. Mohan; Markus Frederich (Marine Environmental Research, 2026)

Stock composition and movement patterns of striped bass in the Saco River Estuary, Maine, USA, using acoustic telemetry - Benjamin P. Gowell; Alexa Cacacie; Jessica B. Maguire; Ashley M. Nicoll; Mike G. Frisk; Keith J. Dunton; Craig Tennenhouse; Jason Doll; John A. Mohan; William Kochtitzky; Michelle Caputo (Estuarine, Coastal and Shelf Science, 2026)

Integrated enzyme-assisted hot water biorefinery for enhanced recovery of bioactive compounds from brown seaweeds - C. S. Tejpal; S. M. Vijayakumar; K. M. Pradeep; Rahman K. Habbeb; T. G. Sumithra; C. O. Mohan; T. K. Anupama; R. Anandan (Journal of Applied Phycology, 2026)

Redefining coastal and marine boundaries through a 50-NM functional threshold for integrated ocean governance - P. Ragavan; R. Ramesh; Sundeep; K. Kathiresan; P. M. Mohan (Hydrobiologia, 2026)

Promoting sustainable pest management through digital decision support tools: Insights from India - Justice A. Tambo; Malvika Chaudhary; Idah Mugambi; Madhu Manjari; Mahesh H. Munireddappa; Kritika Khanna; J.V. Mohan Rao; M. Bheemanna; Prabhuraj Aralimarad; Rajkumar Ramasamy (Agricultural Systems, 2026)

Evolution of Climate Extremes Over the Indian Subcontinent Using a Revised CEI - Thota Mohan; M. Rajeevan; Smrutishree Lenka; Kondapalli Niranjan Kumar; P. Rohini; O. P. Sreejith (International Journal of Climatology, 2026)
Employing observed gridded daily rainfall and temperature datasets for 1971–2022, we developed a revised India Climate Extremes Index ( IndCEI ) to assess long‐term variability in climate extremes across the country. The IndCEI modifies the original CEI framework by integrating seven indicators particularly relevant to the Indian climate system: maximum temperature ( T max ), minimum temperature ( T min ), consecutive dry days (CDD), heavy precipitation events, the Standardised Precipitation–Evaporation Index (SPEI), Heat Index (HI), and Excess Heat Factor (EHF). Results reveal robust and widespread warming signals over India, with significant increases in T max extremes across all four homogeneous regions. Northwestern India (NWI) emerges as the principal hotspot, exhibiting the strongest positive trends in T max , HI, and EHF—indicative of intensifying heat stress and more frequent heatwaves. South Peninsular India (SPI) also shows marked increases in drought‐related extremes (SPEI, CDD). In contrast, Northeast India (NEI) displays heightened short‐duration heavy rainfall events alongside increasing drought episodes, signalling greater hydroclimatic variability. East‐Central India (ECI), the core monsoon zone, presents weaker or inconsistent trends, likely reflecting the influence of monsoon variability and embedded low‐pressure systems. Spatial analyses indicate that both T max and T min extremes have expanded beyond localised pockets, while drought and HI extremes have intensified and spread inland from coastal areas‐creating new hotspots in central and eastern India. At the all‐India scale, IndCEI exhibits a statistically significant increasing trend (~0.36% of area per decade), driven primarily by rising heat stress and drought indicators. Overall, the findings highlight a growing risk of climate extremes, particularly heat, drought, and rainfall across India. The results underscore pronounced regional contrasts: western and southern India are increasingly dominated by heat‐related stress, while Northeastern India faces rainfall‐driven extremes. These expanding hotspots of climate stressors call for region‐specific adaptation strategies, particularly addressing heat in NWI, drought in SPI, and rainfall variability in NEI.

Multifunctional meat packaging in the digital era: a scoping review of innovations, gaps, and future pathways - Kiran Mohan; Naveena B. Maheswarappa; Rituparna Banerjee; Prasad M. Govindaiah (Critical Reviews in Food Science and Nutrition, 2026)

Improving lightning representation in global model through convective cloud based Price and Rind 1992 scheme - M. Sandhya; Greeshma M. Mohan; Saji Mohandas; A. Jayakumar; T.J. Anurose; V.S. Prasad (Science of The Total Environment, 2026)

Influence of larval diet on the life table traits of Chrysoperla zastrowi sillemi using age-stage two-sex life table: insights for mass production - K. T. Shivakumara; T. Venkatesan; S. S. Udikeri; M. C. Keerthi; T. Sudha; M. Mohan; C. Manjunatha; G. S. Guruprasad (Journal of Plant Diseases and Protection, 2026)

Projected twelve-fold growth in municipal solid waste generation calls for urgent techno-policy intervention across urban India - Vinay Yadav; Amar Mohan Shinde; Bholu Ram Yadav; Daya Shankar Pandey; Kamal Jyoti Maji; M. K. Manu; Vipin Singh; Mohit Arora (Journal of Industrial Ecology, 2026)
Contemporary consumption patterns are intensifying the municipal solid waste (MSW) crisis across the Global South. In urban India, encompassing both major metropolitan areas and more than 4,000 statutory towns, MSW has emerged as a major environmental and development challenge, shaped by long-standing systemic inefficiencies in waste management. In this article, we present a data-driven analysis of post-independence trends in MSW generation, waste composition, and urban policy development across India. We show that annual MSW generation has increased approximately tenfold since 1947, reaching about 58.5 million tonnes (Mt). Extrapolation of historical trends suggests that Indian cities could generate about 153 Mt of MSW by 2050. However, under conditions of rapid socioeconomic transformation, more material-intensive consumption trajectories could raise annual MSW generation to 206–287 Mt under modest consumption pathways and to 436–711 Mt under high-consumption lifestyles. This projected five- to twelve-fold increase in annual MSW generation over the coming decades will require major expansion of waste management infrastructure and the implementation of effective techno-policy interventions. We therefore propose a set of systemic interventions to manage projected MSW flows and support a circular urban material system through coordinated implementation from local to national scales. With appropriate contextual adaptation, the insights and strategies developed in this study can help advance circular economy and net-zero ambitions in the MSW sector across the Global South.

Genomic analysis identifies unreported adaptive mutations in monkeypox virus immune evasion genes - Ann Steffi Sharon John; Mirudhula Kamakshi Mohan Ramaswamy; Harihar Balasubramanian; Karthick Selvaraj; Thenmozhi Marudhadurai; M. R. Asraf Sithikka; Gayathri Elangovan; Manojkumar Kumaran; Suvaiyarasan Suvaithenamudhan; Konda Mani Saravanan (Virus Genes, 2026)

Application of time-domain electromagnetic data in 3D mapping of buried paleochannels hosting sandstone type uranium mineralization in Satpura Gonwana basin, India - M. Sridhar; A.K. Maurya; Amaresh Kumar; Rakesh Mohan; Srinjoy Mukharjee; S.K. Dash; R. Mamallan (Journal of Applied Geophysics, 2026)

Derivation of seawater quality criteria for copper, cadmium, zinc, and mercury for the coastal and coral reef ecosystems of Gulf of Mannar, India - C M Ramakritinan; M Anand; L Palanikumar; Manoj Singh; S Manikandan; G Jayanthi; A K Kumaraguru; D Mohan; T Balasubramanian; B R Subramanian (Journal of Earth System Science, 2026)

A curcumin–resveratrol–carnosic acid complex mitigates brain–gut axis disruption in a rodent model of repeated mild traumatic brain injury - Mohind C Mohan; Anjana A S; Deepa Azhchath Vasu; Yadukrishnan M B; Aneesa P A; Tara Sudhadevi; Krishnakumar I M; Baby Chakrapani P S (Metabolic Brain Disease, 2026)

Dual‐Channel Temporal Graph Attention Network for Forecasting Sodium Hazard in Irrigation Water Systems - A. M. Arun Mohan; B. Senthilnayaki; K. R. Mohan Raj; Verma (Irrigation and Drainage, 2026)
Groundwater quality for irrigation is increasingly threatened by overextraction, salinization and agricultural intensification, yet existing sodium hazard prediction methods often fail to capture complex temporal and relational dynamics. This study proposes a Dual‐Channel Temporal Graph Attention Network (DC‐TGAN), integrated with advanced preprocessing and hybrid feature selection, to enhance the prediction of farming water quality characteristics—Kelly's ratio (KR), residual sodium carbonate (RSC), sodium adsorption ratio (SAR), and %sodium (%Na)—in Southern Rajasthan, India's Pratapgarh district. The approach's originality is found in its ability to simultaneously model multivariate spatiotemporal dependencies and optimize convergence through Quokka Swarm Optimization. The model was found to best predict groundwater when using 10 years (2010–2020) of groundwater data, with correlation coefficients ( R 2 ) near to 1.0 and testing RMSE of 0.04 in KR and 0.16 in SAR. On the whole, the DC‐TGAN was superior to the models of random forest, ANN, LSTM and WDO‐ANN with an accuracy of 99.8%, F1‐score of 99.7%, and the T of 0.02 s. These findings indicate that the model can be viewed as a powerful and scalable instrument of timely identifying sodium hazards to contribute to sustainable groundwater management and irrigation planning in semiarid areas.

Agrobacterium-mediated transformation of Chlamydomonas reinhardtii to produce recombinant human serum albumin - Pratheesh Prakasam Thanka; Vineetha Mohan; Muraleedhara Kurup; Menatalla M. Ismail; Mallik Sudhanshu; Abdel-Hamid I. Mourad (Algal Research, 2026)

Opportunities for social sustainability through local governance of mine and quarry restoration - Grace N. Tully; Oliver Holt; Mohan Yellishetty; Megan A. Farrelly; David Whittle; Peter M. Bach (The Extractive Industries and Society, 2026)

Long-term ecological recovery of a minespoil watershed: Hydrological, vegetation, and carbon stock assessment - Jag Mohan Singh Tomar; Anupam Barh; Raj Kumar; Deepak Singh; Ranjeet Singh; Dinesh Jinger; R.K. Singh; Rajesh Kaushal; Sneha Dobhal; M. Madhu (Ecological Engineering, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

High levels of Bt cry toxin resistant allele frequency in South Indian populations of cotton pink bollworm, Pectinophora gossypiella Saunders (Gelechiidae: Lepidoptera) - Suresh R. Jambagi; M. Mohan; T. Venkatesan; K. Muralimohan; D.N. Kambrekar; C.P. Mallapur; Neenu Augustine (Journal of Invertebrate Pathology, 2026)

Assessing carbon farming potential in Victoria, Australia: A statewide perspective - Shushil Giri; Peter M. Bach; Mohan Yellishetty (Journal of Cleaner Production, 2026)

Unveiling the Schottky interface engineering in metal tellurides for scalable hydrogen production - V. Bharathi Mohan; S. Jayachitra; M. Sathish (Chemical Engineering Journal, 2026)

Morpho-molecular characterization of fruit flies (Diptera: Tephritidae) infesting guava and kinnow in Haryana, India - Nachin M. Gowda; Swati Mehra; Balram Sharma; Mohan Sundaramoorthy; Tarun Verma; Nita Lakra; Dalvinder Pal Singh (Phytoparasitica, 2026)

Oral delivery of an ustekinumab biosimilar with bioavailability comparable to subcutaneous administration in healthy human participants - Joshua T. Myers; Alyson Yamaguchi; Kyle Horlen; Leonard C. Fung; April Toledo Vo; Deepa Mohan; Mary Hoopes; Mir Imran; Jacques Van Dam; Ofer M. Gonen; Mir A. Hashim; Arvinder K. Dhalla; et al. (European Journal of Clinical Pharmacology, 2026)

Radiant solutions: Unlocking the mysteries of Mn2+ and Pd2+ with a mobile fluorescence wizard - Virender; Manpreet Kaur; Hari Om; Bakhtiyar Najafov; Ashok Kumar Sharma; Ismayil M. Garazade; M.Fátima C. Guedes da Silva; Armando J.L. Pombeiro; Wei Sun; Brij Mohan (Journal of Hazardous Materials, 2026)

Protected areas influence fire regimes globally - A. Cardil; M. Rodrigues; D. Ascoli; M. Ortega; T. Quiñones; M. Erdozain; I. Oliveras Menor; G.L. Spadoni; J. Ramírez; J.R. Molina; F. Mouillot; C.A. Silva; et al. (Journal of Environmental Management, 2026)

Technology advancements in future waste biorefineries: Focus on low carbon fuels and renewable chemicals - J. Shanthi Sravan; Shivali Sahota; Omprakash Sarkar; M. Venkateswar Reddy; S. Venkata Mohan; Young-Cheol Chang (Fuel, 2026)

Isolation and whole-genome characterization of multidrug-resistant Acinetobacter baumannii from Indian retail meat: unveiling high-risk clones and zoonotic transmission threats via comparative genomics - Vanishree B.; Wilfred Ruban Savariraj; Mohan H. V.; Jaganatha Rao; Porteen Kannan; Anbazhagan Subbaiyan; Sureshkannan S.; Nidhi Sudhakaran P.; Nithya Quintoil M.; Sivachandiran R.; Sivaraman Gopalan Krishnan; Raghavendra G. Amachawadi (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Urdamycin V from Streptomyces sp induces p53 independent apoptosis in cervical cancer cells inconsiderate of HPV status and inhibited growth of gram-positive human pathogens - Vipin Mohan Dan; Rahul Sanawar; Gama M. G. Mohan; Soniya P. Cheriyan; Thankayyan R. Santhosh Kumar (Natural Product Research, 2025)

LIDAR based site assessment for rendezvous, docking and landing applications of autonomous space vehicle - Krishna Mohan; Sreeja S; Ponmalar M (Journal of Space Safety Engineering, 2025)

Mangrove-based carbon market projects: Current trends and future perspectives - Jorge F. Montenegro; Midhun Mohan; Ewane Basil Ewane; Daniel A. Friess; Pandi P. Selvam; Abhilash Dutta Roy; Aaron Althauser; Jacob Tidwell; Julieta Gamboa-Cutz; Caileigh Shoot; Michael S. Watt; Peter I. Macreadie; et al. (Forest Policy and Economics, 2025)

Discrimination of cold-slaughtered versus freshly slaughtered chicken meat using a heat-stable hemoglobin-derived biomarker: Targeted MRM-based quantification and validation - Rituparna Banerjee; Naveena B. Maheswarappa; Potlapati Varakumar; Judy Lalthanmawii; Prasad M. Govindaiah; Balaji M. Belore; Kiran Mohan (Food Chemistry, 2025)

Accelerated breeding modernization: a global blueprint for driving genetic gains, climate resilience, and food security in rice - Sanjay K. Katiyar; Reshmi Rani Das; Lekha T. Pazhamala; Jérôme Bartholomé; Girish Chandel; Atugonza Bilaro; Maxwell Darko Asante; Khandakar Md Iftekharuddaula; Mirza M Islam; Ram Baran Yadaw; Ramlakhan Verma; Thati Srinivas; et al. (Theoretical and Applied Genetics, 2025)
Key message ABM-BOx is a mission-critical transformation engine, built to fast-track genetic gains, boost climate resilience, and modernize outdated breeding programs into agile, data-driven, demand-responsive innovation platforms setting a global benchmark. Abstract Rice plays a central role in global food security as climate threats continue to rise. Fast-tracking genetic gains and developing climate-resilient, market-preferred varieties require a bold, system-wide transformation of rice breeding practices worldwide. Baseline diagnostics of more than 25 national rice breeding programs across the Global South revealed critical bottlenecks: obsolete breeding strategy and scheme, fragmented workflows, limited technology access, and poor integration of seed system. This highlights the urgent need of breeding modernization to tackle rising food security risks. We introduce Accelerated Breeding Modernization-Breeding and Operational Excellence ( ABM-BOx ), a globally scalable framework to transform rice breeding programs into modern, data-driven, impact-oriented systems. ABM-BOx operationalizes a paradigm shift by translating the breeder’s equation into real-world impact through two synergistic engines: Breeding Excellence (BE) and Operational Excellence (OE). BE focuses on enhancing genetic gains through demand-driven breeding, strategic parental selection, recurrent population breeding, simulation-driven breeding scheme optimization, genomic selection, and predictive breeding. These strategies increase selection intensity, selection accuracy and shorten the breeding cycle. OE ensures speed, efficiency, and scalability through speed breeding-field based platforms, smart breeding-digital tools, breeding informatics-AI-powered decision tools, strategic costing-optimizing investments, and resilient seed systems. Additionally, Capacity Reinforcement and Functional Transformation-Accelerated Breeding Modernization (CRaFT-ABM) strengthens institutional capacity by focusing on talent, infrastructure, governance, and networks. More than a framework, ABM-BOx is a mission-critical transformation engine that drives innovation, speed, and impact to empower rice breeding efforts globally.

Date Palm (Phoenix dactylifera L.) Microsatellites: Genome-Wide Resource for Diversity Analysis and Cross-Transferability in Arecaceae - Darshan T. Dharajiya; Bhemji P. Galvadiya; Piyush Verma; Anuj Kumar Singh; Kapil Mohan Sharma; D. A. Baidiyavadra; C. M. Muralidharan; Kapil K. Tiwari (Sugar Tech, 2025)

Microsatellite markers development and molecular fingerprinting of cashew cultivars - Siddanna Savadi; Gokul Mohan; K. Manoj; Manju Manuel; B. M. Muralidhara; Babli Mog; Jamboor Dinakara Adiga (Molecular Biology Reports, 2025)

UAV-supported mangrove restoration: nature-based solutions for controlling vector-borne disease incidence - Midhun Mohan; Shalini A. L. King; Lara G. Moussa; Michael S. Watt; Emma M. Awuku-Sowah; Gregory F. Albery; James Kairo; A. Aldrie Amir; Julius Sila; Peter I. Macreadie (Environmental Monitoring and Assessment, 2025)

Methods for precipitating plasma proteins for stable isotope analysis of elasmobranch blood - Alexander M. Rubin; Sunita R. Shah Walter; John A. Mohan; Aaron B. Carlisle (Journal of Experimental Marine Biology and Ecology, 2025)

Similar size distributions of casein micelles determined by cryo-electron microscopy and nanoparticle tracking analysis - Maneesha S. Mohan; Isabella Loughland; Jared K. Raynes; Federico M. Harte; Carl Holt (International Dairy Journal, 2025)

Understanding the working of magnetic COFs in the extraction and determination of target contaminants for food safety - Brij Mohan; Rakesh Kumar Gupta; Ismayil M. Garazade; Gurjaspreet Singh; Armando J.L. Pombeiro; Bakhtiyar Najafov; Wei Sun (Food Chemistry, 2025)

Hybrid deep learning with a fusion model of weather and soil-based multi-crop recommendations for improving crop sustainability - Mohan M; S. Anandamurugan (Theoretical and Applied Climatology, 2025)

Analysis of Two Heavy Rainfall Episodes in May 2022 and June 2022 in Southern Parts of Assam, Northeast India - S. I. Laskar; H. Baisya; S. Das; A. Sandeep; M. Mohapatra; K. N. Mohan (Pure and Applied Geophysics, 2025)

Frequency of γ-H2AX foci, micronucleus formation, and radiation dose to the blood lymphocytes in pediatric and adult participants underwent computed tomography imaging - Divya K. Mohan; Nandhini K.; Aishwarya S.; Senthil Kumar M.; Swetha K.; Akshaya J.; Sudha Pattan; Venkata Sai P.M.; Venkateswarlu Raavi; Venkatachalam Perumal (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2025)

Anthropogenic influence on black carbon concentrations in pristine Antarctic environment - Sathish Mohan Botsa; M. P. Raju; A. K. Tiwari; NS Magesh (Air Quality, Atmosphere & Health, 2025)

Protocol for the in-situ U–Pb dating of zircon with high sample throughput and spatial resolution using LA-HR-ICP-MS: A case study on detrital zircon from the Cuddapah Basin - Sameer Ranjan; Ajay Dev Asokan; M Ram Mohan; M Satyanarayanan; D Srinivasa Sarma (Journal of Earth System Science, 2025)

Evaluating the impact of aircraft observations on meteorological forecasts over the Indian subcontinent during southwest monsoon - Kumarjit Saha; S Indira Rani; S Desamsetti; Greeshma M Mohan (Journal of Earth System Science, 2025)

Seasonal dynamics of dissolved and particulate organic carbon in nearshore waters of the Andaman Islands - P. M. Mohan; R. Karuna Kumari; N. V. H. K. Chari; Sai Elangovan S.; J. Joyson Joe Jeevamani; Mamidala Harikrishna Prasad; Supriyo Chakraborty; V. Sachithanandam (Frontiers in Marine Science, 2025)
This study investigates the seasonal and spatial variability of hydrochemical parameters and organic carbon pools between the South Andaman Islands (SAI) and North Andaman Islands (NAI) under contrasting monsoonal regimes. Seawater temperature (26.1 – 33.5°C) was consistently higher in SAI due to reef-associated stratification, while NAI exhibited greater variability. Salinity (25.2 – 35.9) and pH were more stable in SAI, whereas NAI showed lower values and higher variability driven by freshwater inputs from the Bay of Bengal river systems. Turbidity and dissolved inorganic nutrients (DIN, DIP, DSi) were significantly higher in NAI, reflecting strong terrestrial and riverine influence. Dissolved organic carbon (DOC; 103 – 772 µM) and particulate organic carbon (POC; 22 – 168 µM) concentrations were consistently higher in NAI, particularly during the spring intermonsoon (SIM) and northeast monsoon (NEM), while SAI exhibited lower but more variable concentrations linked to reef metabolism. Seasonal drivers included freshwater and terrestrial inputs enhancing DOC during SIM and NEM, and monsoon-induced mixing reducing concentrations during the southwest monsoon (SWM). POC levels were enriched in NAI throughout, whereas SAI showed greater variability related to reef-derived particulate cycling. The POC: DOC ratio (0.04 – 0.83) highlighted contrasting biogeochemical regimes, with NAI dominated by particulate-rich terrestrial inputs and SAI characterized by variable phytoplankton- and reef-driven processes. These findings emphasize the role of monsoonal forcing in shaping carbon dynamics across the Andaman Islands and the contrasting influence of terrestrial inputs in NAI versus reef-associated processes in SAI, with implications for regional carbon cycling and ecosystem functioning.

LP-53 Evaluation of the Mutagenic Potential of 1-Cyclopentyl-4-Nitrosopiperazine Nitrosamine in Human Lymphoblastoid TK6and CHO-K1 Cells - M. Shameer P; T. Pradeep; M. Rajini; A. Mariappan; S. Sandhya; G. Kulavardhan; M. Sumithra; R. Harika; A. Varun; K. Mohan; V. Deepa (Toxicology Letters, 2025)

Neurobehavioural assessment of hesperitine and epigallocatechin gallate in aluminium chloride-induced neurotoxicity in zebrafish model - A. Madeswaran; V. Keerthana; M. Shelpa; S. Kaladharan; B. Varunkumar; S. Mohan (Next Research, 2025)

The role of atmospheric and oceanic factors on the record low Antarctic sea ice extent of 2023 - M. Swathi; Avinash Kumar; Juhi Yadav; Rahul Mohan (Global and Planetary Change, 2025)

Improvements in the prediction of extreme rainfall events with nested high-resolution rapid refresh modelling system over the Indian Himalayan region - K.B.R.R. Hari Prasad; Ashish Routray; Greeshma M. Mohan; V.S. Prasad (Atmospheric Research, 2025)

Insecticide degradation potential of aphid associated bacteria - Mahesh S. Yandigeri; Sampada N.; Manoj Kumar Solanki; Sanjay Yalashetti; M. Mohan; G. Sivakumar; B.S. Manjunatha; S.N. Sushil (Biocatalysis and Agricultural Biotechnology, 2025)

Local Delivery of Non-opioid Analgesic Microparticles to Modulate Post-surgical Pain - Prerna Mohan; Jeladhara Sobhanan; Caitlyn M. Gaffney; Nitisha Mehrotra; Fernando J. Cabrera; Richard Lee; Aparna Adumbumkulath; Eric Haas; Andrew J. Shepherd; Crystal S. Shin; Ghanashyam Acharya (Pharmaceutical Research, 2025)

Evaluation of policy interventions to mitigate the prevalence of household air pollution due to biomass fuel and its associated health risks in rural India - Yaparla Deepthi; Amit Passi; Chithra V. S; Lekshmi Mohan V; Smaranika Panda; S. M. Shiva Nagendra (Air Quality, Atmosphere & Health, 2025)

Validation and assessment of Potential Fishing Zone (PFZ) dynamics along the southwest coast of India through environmental proxies and trophic guild analysis - Dhanya Mohan Lal; Harisha; Alakes Samanta; Sudheer Joseph; S Suresh Kumar; Sanjiba Kumar Baliarsingh; T M Balakrishnan Nair (Environmental Impact Assessment Review, 2025)

Fabrication of CoTe-phosphorus doped g-C3N4 photocatalytic engine: A leap towards eco-friendly hydrogen production - V. Bharathi Mohan; S. Jayachitra; P. Devi; P. Murugan; M. Sathish (Chemical Engineering Journal, 2025)

Enhancement of genetic gain for early seedling vigor traits through marker-assisted pedigree selection in rice (Oryza sativa L.) - Sudhamani Kalluru; Issa Keerthi; Madhavilatha Kommana; D. M. Withanawasam; Eswarayya Ramireddy; D. Mohan Reddy; V. Umamahesh; Lakshminarayana R. Vemireddy (Physiology and Molecular Biology of Plants, 2025)

Zircon U-Pb age and petrogenetic constraints on granitic magmatism from the southwestern Chhotanagpur Granite Gneiss Complex: Implications for Proterozoic crustal growth in the Central India - Mohammad Qasim; Satya Narayana Mahapatro; Sameer Ranjan; Ajay Dev Asokan; D. Srinivasa Sarma; M. Ram Mohan (Precambrian Research, 2025)

Prospecting indigenous Bt isolates for bioinsecticidal efficiency against soil-borne white grub, Holotrichia serrata (F.) (Coleoptera: Scarabaeidae) - M. Manoj; K. Tamilvendan; Mohan Chavan; G. Selvakumar; K. Nagaraju; C. Manjunatha (Journal of Asia-Pacific Entomology, 2025)

Influence of floral traits on visitation patterns in a miniature tropical stingless bee, Tetragonula iridipennis - Asmi Jezeera M.; Kavya Mohan N.; Sreyas Sreekumar; Almut Kelber; Hema Somanathan (The Science of Nature, 2025)

Eco-friendly structures for sustainable mangrove restoration - Midhun Mohan; Pandi P. Selvam; Ewane Basil Ewane; Lara G. Moussa; Emma F. Asbridge; Stacey M. Trevathan-Tackett; Peter I. Macreadie; Michael S. Watt; Lucy Gwen Gillis; Francoise Cabada-Blanco; Ian Hendy; Eben North Broadbent; et al. (Science of The Total Environment, 2025)

Assessing repurposing options for abandoned mines and quarries in Victoria, Australia using spatial MCDA - Shushil Giri; Oliver S. Holt; Grace Tully; Alec Miller; Mohan Yellishetty; David Whittle; Peter M. Bach (Resources, Conservation and Recycling, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Fidelity of coupled hindcast simulations in representing intraseasonal biases over South Asia - D. Nagarjuna Rao; T. S. Mohan; Ankur Gupta; Kondapalli Niranjan Kumar; Akhilesh Mishra; Imranali M. Momin; Saji Mohandas; Ashis K. Mitra; V. S. Prasad (Climate Dynamics, 2025)

Trends in Antarctic Sea Ice and Albedo: Impacts of Ocean‐Atmospheric Processes - M Swathi; Aakriti Srivastava; Avinash Kumar; Juhi Yadav; Dinesh Chandra Gupta; Rahul Mohan (International Journal of Climatology, 2025)
Surface albedo (SAL), a critical factor in climate studies, significantly impacts the Earth's radiation budget and sea ice dynamics. The long‐term spatial and temporal variability of Antarctic SAL were derived from the third edition of the Cloud, Albedo, and Surface Radiation Dataset (CLARA‐A3). The analysis focused on spring and summer across five longitudinal sectors around Antarctica. The relationships of sea ice concentration (SIC) and SAL with climatic variables such as sea surface temperature (SST), 2 m air temperature (T2m), turbulent heat flux, and total cloud cover are explored in detail. The study examined SAL changes in two distinct timescales, pre‐2015 (1979–2015) and post‐2015 (2016–2021), to understand sea ice variations and trends in Antarctic climate change. The study revealed contrasting summer SAL trends, with a positive trend pre‐2015 and a decreasing trend post‐2016 across most of Antarctica, except the Amundsen‐Bellingshausen Sea, which showed an opposite trend. West Antarctica exhibited higher SAL compared to East Antarctica. SAL and SIC were significantly negatively correlated with SST, T2m, and turbulent heat flux across all sectors. Cross‐seasonal lead–lag analysis indicated that increased turbulent heat flux was followed by an increase in SAL after 1–5 months. Wind patterns showed that winds from higher to lower latitudes increased SIC and SAL, while winds from lower to higher latitudes reduced SIC. Post‐2015, notable wind direction reversals were observed in the Antarctic Peninsula during spring. Sectors with higher cloud cover absorbed more ocean heat, reducing turbulent heat flux and affecting SAL. Overall, post‐2015 observations highlighted major shifts in sea ice dynamics and SAL trends during both spring and summer seasons. The SIC decreased markedly across all sectors, with the Weddell Sea showing the most significant reduction. This study highlights regional and seasonal variations in SAL and its interactions with SIC and climatic factors, emphasising shifts in trends post‐2015.

Assessment of sweetpotato germplasm for selection of day-neutral genotypes for tropical India - Shirly Raichal Anil; M. N. Sheela; C. Mohan; A. N. Jyothi; C. Visalakshi Chandra; S. Shanawas; J. Sreekumar (Euphytica, 2025)

Iron oxide nanoparticles as efficient adsorbents for malachite green dye removal: Isotherms, kinetics, and thermodynamics analysis - Abhishek Kumar; Hara Mohan Jena; Krunal M. Gangawane (Environmental Science and Pollution Research, 2025)

First metabolic profiling of Indian wild edible mushroom Amanita hemibapha reveals antimicrobial compounds that infers selective activity against gram-positive human pathogens - Gama Mohan M Geetha; Anagha Bindu; Ratheesh Sugathan; Vipin Mohan Dan; Chittethu Kunjan Pradeep (Natural Product Research, 2025)

Early insights into the seasonal and spatial distribution of white sharks (Carcharodon carcharias) along the Maine coastline - Matthew M. Davis; Megan V. Winton; John A. Mohan; Joseph D. Iafrate; James A. Sulikowski; Blaise P. Jenner; Ashleigh J. Novak; Victoria Migneco; Tobey H. Curtis; Chip Michalove; Gregory B. Skomal (Frontiers in Marine Science, 2025)
While significant progress has been made to characterize life history patterns, movement ecology, and regional estimates of abundance of white sharks ( Carcharodon carcharias ) in the Western North Atlantic (WNA), patterns of spatial distribution remain relatively unknown in the northern Gulf of Maine. In this study, we utilize data collected from multiple acoustic telemetry projects from 2012-2023 to assess the spatiotemporal distribution of white sharks along sections of the Maine coastline and regional offshore waters. Acoustic receivers were deployed each year from 2012-2019 (mean number of receivers ± SD: 11 ± 4), and effort increased following the first-ever white shark related fatality in Maine in 2020 (2020-2023: 40 ± 15). In total, 107 white sharks tagged by researchers in the WNA were detected, with the majority (n = 90) detected in shallow (<50 m depth) waters post-2019. Reflective of the tagged population at-large, total length of individuals ranged from 2.1 to 4.9 m, with most individuals estimated to be in the juvenile or subadult life stages. White sharks were detected between the months of May-December, with peaks between July and September, and were observed in close proximity to several of Maine’s western beaches and islands/outcroppings, with higher numbers observed at several sites in eastern Casco Bay. Although the overall quantity of detections was relatively low when compared to white shark aggregation sites in other regions, this study provides baseline information on the presence of this species in the northern Gulf of Maine. While future research should include expanded receiver coverage in eastern Maine and the use of additional tagging technologies, this study contributes early insights for informing marine spatial planning, fisheries management, and conservation strategies for white sharks in the region.

Retraction notice to “Pyto-Architechture of Ag, Au and Ag–Au bi-metallic nanoparticles using waste orange peel extract for enable carcinogenic Congo red dye degradation” [Environ. Res. 242 (2024) 117625] - B. Christina; K. Thanigaimani; R. Sudhakaran; S. Mohan; Natarajan Arumugam; Abdulrahman I. Almansour; Sakkarapalayam M. Mahalingam (Environmental Research, 2025)

Cognizance about sea water intrusion by chemical analysis in coastal aquifer of southeast coast of India - V. Baskaran; M. Sridharan; R. Saravanane; S. Mohan (International Journal of Energy and Water Resources, 2025)

Multi-sensor analytics for mapping chromite mineralization zones in Nuggihalli Schist Belt, Southern India: Inferences from ASTER, Sentinel-2A, and Landsat 8 satellite images - V. Deepchand; A. Haritha; M. Monisha Mohan; V.J. Rajesh; K.S. Sajinkumar; R.B. Binoj Kumar (Advances in Space Research, 2025)

Efficacy of Duddingtonia flagrans spores fed in trace mineral mix to lambs in reducing the development of gastrointestinal nematode larvae in feces - Joan M. Burke; Suman Rohila; Elisa Preston; Cathleen C. Williams; Clare M. Scully; Brooke A. Delcambre; Katherine H. Petersson; Elizabeth Kass; Mohan Acharya; James E. Miller; Adriano F. Vatta (Veterinary Parasitology, 2025)

Mangrove-based carbon market projects: What stakeholders need to address during pre-feasibility assessment - Ewane Basil Ewane; Pandi P. Selvam; Reem AlMealla; Michael S. Watt; Pavithra S. Pitumpe Arachchige; Barbara Bomfim; Wan Shafrina Wan Mohd Jaafar; Soheil Salehian; Tarig Ali; Nithyanandan Manickam; Meshal M. Abdullah; Sophie Westover; et al. (Journal of Environmental Management, 2025)

Citrinin (CIT), a polyketide mycotoxin from a mangrove endophytic fungus Penicillium rubens EF 363 and its bioactive potential - M. R. Revathy; Anjali S. Mohan; Dhanya Kesavan; M. Dhaneesha; P. V. Santhini; Muralidharan Vanuopadath; Bipin G. Nair; Remington X. Poulin; T. P. Sajeevan; Rosamma Philip (Vegetos, 2025)

Modelling of raindrop size distribution using optimized kernel fuzzy c-means clustering algorithm - M Sivagami; Rishabh Dhoot; Saumay Agrawal; Shushil Kumar; L Shyamala; E Arunbabu; K Mohan (Theoretical and Applied Climatology, 2025)

Thermodynamics link with lightning incidents in Tamil Nadu, India - S Kokilavani; V Geethalakshmi; S P Ramanathan; S D Pawar; V Gopalakrishnan; Somnath Mahapatra; Jayesh Chhagan Dhangar; Ga Dheebakaran; N K Sathyamoorthy; M Selva Kumar; S Mohan Kumar; Manoj A Domkawale (Journal of Earth System Science, 2024)

Zircon U-Pb-Hf isotopes constraints on the petrogenesis of Neoarchean granitic rocks from the Northeastern part of the Eastern Dharwar Craton, Southern India - B. Vikram Raju; Ajay Dev Asokan; Xiao-Ping Xia; Zexian Cui; Arathi G. Panicker; M. Ram Mohan (Lithos, 2024)

Characterizing the dynamics of climate and native desert plants in Qatar - Meshal Abdullah; Ammar Abulibdeh; Sophia Ghanimeh; Helmi Hamdi; Hezam Al- Awah; Talal Al-Awadhi; Midhun Mohan; Zahraa Al-Ali; Abdullah Sukkar; Ahmed M. El Kenawy (Journal of Arid Environments, 2024)

Immuno-pathogenesis study of local infectious bronchitis virus G1-1 lineage variant showed altered tissue tropism in experimental broiler chickens - Megha Sharma; Faslu A. T. Rahman; Gaurav Sharma; Sohini Dey; Madhan Mohan Chellappa; Anshuk Sharma; Kuldeep Dhama; G. Saikumar; Asok M. Kumar (Veterinary Research Communications, 2024)

Effect of Storage Temperature and Containers on Date Palm (Phoenix dactylifera L.) Pollen Viability and Post-storage Pollination - Kapil Mohan Sharma; Devshi A. Baidiayavadra; C. M. Muralidharan; C. N. Panchal; Piyush Verma (Sugar Tech, 2024)

Identification and characterization of potential sources of waterlogging tolerance in Vigna species as revealed by physiological, biochemical and gene expression profiling - Sandeep Kumar; Chandra Mohan Singh; Mukul Kumar; Shalini Purwar; Hitesh Kumar; Anuj Mishra; Ashutosh Rai; Vaishali Gangwar; Ramkrishanan M. Nair; Aditya Pratap (Journal of Plant Biochemistry and Biotechnology, 2024)

Remote Sensing-Based Ecosystem Monitoring and Disaster Management in Urban Environments Using Machine Learnings - M. Mohan; Anila Macharla; Parthasarathi P.; Bediga Sharan; A. Nageswaran; Balajee R. M. (Remote Sensing in Earth Systems Sciences, 2024)

One-pot hydrothermal synthesis of 3D garland BiOI, spherical ZnO, and CNFs onto Ni foam: Supercapacitor performance with enhanced electrochemical properties - N. Ramesh Reddy; A. Sai Kumar; P. Mohan Reddy; Nipa Roy; Suvardhan Kanchi; Raghava Reddy Kakarla; Jae Hak Jung; Tejraj M. Aminabhavi; Sang Woo Joo (Journal of Environmental Management, 2024)

Harnessing multifunctional antimony doped Tin (IV) sulfide nanosheets for chlorpyrifos degradation and hydrogen evolution - G. John; Harshavardhan Mohan; M. Navaneethan; Seung Yoon Ryu; Byung-Taek Oh; P. Justin Jesuraj (Chemical Engineering Journal, 2024)

Comparison of Two-Moment and Three-Moment Bulk Microphysics Schemes in Thunderstorm Simulations over Indian Subcontinent - Chandrima Mallick; Ushnanshu Dutta; Moumita Bhowmik; Greeshma M. Mohan; Anupam Hazra; Rakesh Ghosh; S.D. Pawar; Jen-Ping Chen (Atmospheric Research, 2024)

Rising dynamics of particle-laden bubbles in presence of surfactant and turbulence - Syamsundar M. Murali Mohan; Zhengbiao Peng; Elham Doroodchi (Minerals Engineering, 2024)

Boosting the response characteristics towards rapid detection of NO2 gas molecules utilizing 2D - WS2/rGO hybrid nanocomposites at ambient environment - D. Simon Patrick; J. Archana; M. Navaneethan; M. Krishna Mohan (Journal of Environmental Chemical Engineering, 2024)

Genetic Profiling of Spodoptera litura (Noctuidae: Lepidoptera) in Indian Sub-Tropical Sugar Beet - Santeshwari Srivastava; Varucha Misra; Arun Baitha; Himanshu Pandey; S. N. Sushil; M. Mohan; A. D. Pathak; Sangeeta Srivastava; Dinesh Singh; Ashutosh Kumar Mall (Sugar Tech, 2024)

Emergence of Basil Downy Mildew in India: need more domestic vigilance to combat spread of Peronospora belbahrii - B. Pushpavathi; M. Madhavi; Rajender Jatoth; J. Chandrakala; P. Narayan Reddy; P. Jagan Mohan Rao (Vegetos, 2024)

Contrasting response of regional spring Arctic Sea ice variations on Indian summer monsoon rainfall - Juhi Yadav; Avinash Kumar; Seong-Joong Kim; Rohit Srivastava; Rahul Mohan; M. Ravichandran (Remote Sensing of Environment, 2024)

Transition from vertical to horizontal tectonic regime during the Paleoarchean-Mesoarchean: Evidence from mafic-ultramafic rocks of the Holenarsipur Greenstone Belt, Western Dharwar Craton, Southern India - Arathi G. Panicker; M. Ram Mohan; Ravi Shankar (Precambrian Research, 2024)

Effects of Soil Application of Nanobiochar-Based Nitrogen and Potassium Fertilizers on the Growth and Yield of Groundnut (Arachis Hypogaea L.) - K. Nagaraju; T. N. V. K. V. Prasad; M. Sreenivasa Chari; Y. Reddi Ramu; B. Ramana Murthy; M. V. S. Naidu; G. P. Leelavathy; P. Ram Mohan; A. G. Damu; D. Gopal (Journal of Soil Science and Plant Nutrition, 2024)

Ecotourism and mangrove conservation in Southeast Asia: Current trends and perspectives - Austin Blanton; Ewane Basil Ewane; Freddie McTavish; Michael S. Watt; Kerrylee Rogers; Redeat Daneil; Irene Vizcaino; Ana Novo Gomez; Pavithra S. Pitumpe Arachchige; Shalini A.L. King; G.A. Pabodha Galgamuwa; Martha Lucia Palacios Peñaranda; et al. (Journal of Environmental Management, 2024)

Corrigendum to “Isobutanol production by Candida glabrata – A potential organism for future fuel demands” [Fuel 306 (2021) 121634] - Nair M Lakshmi; Mohan Binoop; Chandrasekharan Nair Salini; Narisetty Vivek; Raveendran Sindhu; Ashok Pandey; Parameswaran Binod (Fuel, 2024)

Petrogenesis of submarine volcanic arc rocks from Andaman subduction zone, Northeast Indian Ocean: Constraints from slab components and mantle wedge characteristics - Bhagyashree Doley; Abhishek Saha; M. Ram Mohan; Koushick Sen; Aditya Peketi (Chemical Geology, 2024)

Cytokinin oxidase2-deficient mutants improve panicle and grain architecture through cytokinin accumulation and enhance drought tolerance in indica rice - Afreen Rashid; V. Mohan M. Achary; M. Z. Abdin; Sangeetha Karippadakam; Hemangini Parmar; Varakumar Panditi; Ganesan Prakash; Pooja Bhatnagar-Mathur; Malireddy K. Reddy (Plant Cell Reports, 2024)

Unraveling the spawning and reproductive patterns of tomato hind grouper, Cephalopholis sonnerati (Valenciennes, 1828) from south Kerala waters - Ponni J. Mohan; M. K. Anil; A. Gopalakrishnan; Shoji Joseph; Devika Pillai; A. Mariyam Fazula; P. Praveen Prasannan (Journal of Fish Biology, 2024)
The objective of this study is to provide information on the reproductive biology of tomato hind grouper, Cephalopholis sonnerati (Valenciennes, 1828) for conservation and management purposes. Fish caught by artisanal fishermen from September 2019 to August 2021 were analysed. A total of 280 females, 31 males, and 4 transitional and 178 sex‐undetermined fish were analysed. The female to male sex proportion was 9:1, and the fish reached a maximum total body length of 38.5 and 54.5 cm for females and males, respectively. The following microscopic stages were identified: immature, developing, ripe, running ripe/releasing, and spent in both males and females. Several asynchronous development patterns were observed in the studied gonads, including multiple oocyte stages and early and advanced stages of sexual transition. High gonadosomatic index (GSI) for both males and females was recorded in March, May, and November. Running ripe and releasing stages in females were identified in the months from March to June, which indicates the spawning season. The absolute and relative fecundity of the species ranged from 162,723 ± 207,267 and 239 ± 285, respectively. An exponential relationship was found between fecundity and total body length (TL), fecundity and total body weight (TW), and fecundity and gonad weight (GW).

Editorial: Research advances from Larsemann Hills, Antarctica: International cooperation and future prospects (Part-2) - Anand K. Singh; Shailendra Saini; Yogesh Ray; Svetlana Grigoreva; Xiangbin Cui; Xianglan Li; Rahul Mohan; M. Javed Beg; Rasik Ravindra (Polar Science, 2024)

Harnessing nature's arsenal: Ochrobactrum bacteria metabolites in the battle against root- knot nematode – Insights from in vitro and molecular docking studies - V.P Krithika; Ganeshan Shandeep; Anita Bellie; J. Gulsar Banu; Jayakanthan Mannu; M. Suganthy; V. Gomathi; D. Uma; Prasanthrajan Mohan (Journal of Invertebrate Pathology, 2024)

Diversity of culturable gut bacteria in natural aphid populations and their contribution to insecticide degradation - Mahesh S. Yandigeri; Manoj Kumar Solanki; Sanjay Yalashetti; Sampada N; Mohan M; Sivakumar G; Sunil Joshi; Satya Nand Sushil (Biocatalysis and Agricultural Biotechnology, 2024)

Unveiling the Bioprospecting Efficacy and Textile Dyeing of a Novel Endophytic Mycobial Red Pigment - Israel Mani; Myithili Thangavel; Akash Surendrababu; M. Joe Xavier Sneha; Rajakrishnan Rajagopal; Ahmed Alfarhan; Nagendraprabhu Ponnuraj; Mohan Pandi (Indian Journal of Microbiology, 2024)

Investigating the Phi Use Efficiency of a NADP Utilizing Phosphite Dehydrogenase in Rice - Dipanwita Datta; Mrinalini Manna; Hemangini Parmar; Sangeetha Karippadakam; Afreen Rashid; Sahil Mehta; Shambhu Krishan Lal; Ajay K. Venkatapuram; Jitender Singh; Malireddy K. Reddy; Srinivas Patnaik; V. Mohan M. Achary (Journal of Plant Biology, 2024)

Navigating water scarcity: rainfall considerations to optimize native vegetation growth in arid lands - Meshal M. Abdullah; Amjad T. Assi; Zahraa M. Al-Ali; Rusty A. Feagin; Talal Al-Awadi; Sara Al-Naabi; Mansour T. Abdullah; Midhun Mohan; Steve Whisenant (Environment, Development and Sustainability, 2024)

Geochemical dichotomy of Tethyan oceanic mantle and the supercontinent connection: Insights from Os isotopic signatures of mantle peridotites from Naga Hills ophiolite - A. Verencar; A. Saha; S. Ganguly; M. Satyanarayanan; M. Ram Mohan (Gondwana Research, 2024)

Monitoring genetic transformation with RUBY visible reporter in Nicotiana tabaccum L. - Phanikanth Jogam; Vaishnavi Anumula; Dulam Sandhya; M. Manokari; Ajay Kumar Venkatapuram; V. Mohan Murali Achary; Mahipal S. Shekhawat; Venkataiah Peddaboina; Venkateswar Rao Allini (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

An improvement in water stress tolerance in rice by altering morpho-physiological and biochemical mechanisms using root colonizing endophyte Piriformospora indica - S. Lekshmi Mohan; R. Beena; M. Joy (Vegetos, 2024)

Chemical composition and biological activities of Lonicera caprifolium L. (Caprifoliaceae) essential oil - Anjali A. Gavit; Manish B. Gagrani; Shailendra S. Gurav; M. Ayyanar; Vishal G. Beldar; Anilkumar U. Tatiya; Sanjay J. Surana; Sandip D. Firke; Mohan G. Kalaskar (Natural Product Research, 2024)

Exploring preferences for improved fish species among farmers: A discrete choice experiment applied in rural Odisha, India - Timothy Manyise; Rodolfo Dam Lam; Denise P. Lozano Lazo; Arun Padiyar; Neeta Shenoy; Mohan V. Chadag; John A.H. Benzie; Cristiano M. Rossignoli (Aquaculture, 2024)

Effect of chronic low-dose treatment with chitooligosaccharides on microbial dysbiosis and inflammation associated chronic ulcerative colitis in Balb/c mice - K M Rajesh; Manas Kinra; Niraja Ranadive; Goutam Mohan Pawaskar; Jayesh Mudgal; Ritu Raval (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
The study aimed to investigate the potential of low dose chitooligosaccharide (COS) in ameliorating dextran sodium sulfate (DSS) induced chronic colitis by regulating microbial dysbiosis and pro-inflammatory responses. Chronic colitis was induced in BALB/c mice by DSS (4% w/v, 3 cycles of 5 days) administration. The mice were divided into four groups: vehicle, DSS, DSS + mesalamine and DSS+COS. COS and mesalamine were administered orally, daily once, from day 1 to day 30 at a dose of 20 mg/kg and 50 mg/kg respectively. The disease activity index (DAI), colon length, histopathological score, microbial composition, and pro-inflammatory cytokine expression were evaluated. COS (20 mg/kg, COS Low ) administration reduced the disease activity index, and colon shortening, caused by DSS significantly. Furthermore, COS Low restored the altered microbiome in the gut and inhibited the elevated pro-inflammatory cytokines (IL-1 and IL-6) in the colon against DSS-induced chronic colitis in mice. Moreover, COS Low treatment improved the probiotic microflora thereby restoring the gut homeostasis. In conclusion, this is the first study where microbial dysbiosis and pro-inflammatory responses were modulated by chronic COS Low treatment against DSS-induced chronic colitis in Balb/c mice. Therefore, COS supplementation at a relatively low dose could be efficacious for chronic inflammatory bowel disease.

The strict regulation of HIF-1α by non-coding RNAs: new insight towards proliferation, metastasis, and therapeutic resistance strategies - Sabrean Farhan Jawad; Farag M. A. Altalbawy; Radhwan M. Hussein; Ali Abdulhussain Fadhil; Mohammed Abed Jawad; Rahman S. Zabibah; Tasneem Younus Taraki; Chakrabhavi Dhananjaya Mohan; Kanchugarakoppal S. Rangappa (Cancer and Metastasis Reviews, 2024)

Efficient synthesis of 3D ZnO nanostructures on ITO surfaces for enhanced photoelectrochemical water splitting - N. Ramesh Reddy; A. Sai Kumar; P. Mohan Reddy; Raghava Reddy Kakarla; Jae Hak Jung; Tejraj M. Aminabhavi; Sang Woo Joo (Journal of Environmental Management, 2024)

Concurrent reduction of the fume and Cr (VI) concentrations of inhalable and respirable particle using a new covered stainless-steel SMAW electrode - M. Rahul; S.P. Sivapirakasam; Mohan Sreejith; B.R. Vishnu; Krishna Vijayakumar (Journal of Environmental Chemical Engineering, 2024)

RETRACTED: Pyto-Architechture of Ag, Au and Ag–Au bi-metallic nanoparticles using waste orange peel extract for enable carcinogenic Congo red dye degradation - B. Christina; K. Thanigaimani; R. Sudhakaran; S. Mohan; Natarajan Arumugam; Abdulrahman I. Almansour; Sakkarapalayam M. Mahalingam (Environmental Research, 2024)

Appraisal of 2004 tsunami induced shoreline change in South Andaman, India using DSAS - G. Narshimulu; V. Shiva Shankar; Neelam Purti; K. Dharanirajan; P. M. Mohan; Pearl Devdas (Journal of Coastal Conservation, 2024)

Unleashing the room temperature boronization: Blooming of Ni-ZIF nanobuds for efficient photo/electro catalysis of water - G. John; S. Priyadarshini; Anandha babu; Harshavardhan Mohan; Byung-Taek Oh; M. Navaneethan; P. Justin Jesuraj (Chemosphere, 2024)

Ultrasensitive and reversible NO2 gas sensor based on SnS2/TiO2 heterostructures for room temperature applications - P. Bharathi; S. Harish; M. Shimomura; M. Krishna Mohan; J. Archana; M. Navaneethan (Chemosphere, 2024)

Review of estimation of soil moisture using active microwave remote sensing technique - M. Akash; P. Mohan Kumar; Pradeep Bhaskar; P.R. Deepthi; Anu Sukhdev (Remote Sensing Applications: Society and Environment, 2024)

Clinical Utility of Pro-inflammatory Oligomeric Glycoprotein Tenascin-C in the Diagnosis of Seropositive and Seronegative Rheumatoid Arthritis - Sachin Dominic; K. S. S. Sai Baba; N. N. Sreedevi; Arshi Sanober; Liza Rajasekhar; Siraj Ahmed Khan; Noorjahan Mohammed; M. Vijaya Bhaskar; Iyyapu Krishna Mohan (Indian Journal of Clinical Biochemistry, 2024)

Assessing ecological connectivity of blacktip sharks (Carcharhinus limbatus) in the Gulf of Mexico using stable isotope analysis of multiple tissues - Addie L. Binstock; Travis M. Richards; Kesley Gibson-Banks; J. Marcus Drymon; R.J. David Wells; John A. Mohan (Fisheries Research, 2023)

Editorial: Research advances from Larsemann Hills, Antarctica: International cooperation and future prospects - Anand K. Singh; Shailendra Saini; Yogesh Ray; Svetlana Grigoreva; Xiangbin Cui; Xianglan Li; Rahul Mohan; M. Javed Beg; Rasik Ravindra (Polar Science, 2023)

Simultaneous removal of selenium and microbial contamination from drinking water using modified ferrihydrite-based adsorbent - Darina Smržová; Prajakta Mohan Ramteke; Petra Ecorchard; Jan Šubrt; Petr Bezdička; Denisa Kubániová; Martin Kormunda; Roman Maršálek; Xenia Vislocká; Anna Vykydalová; Sunit Kumar Singh; Roshan Wathore; et al. (Journal of Water Process Engineering, 2023)

Correction: Exogenous delivery of dsRNA for management of mungbean yellow mosaic virus on blackgram - K. Kamesh Krishnamoorthy; V. G. Malathi; P. Renukadevi; S. Mohan Kumar; M. Raveendran; M. Sudha; N. Manivannan; G. Karthikeyan (Planta, 2023)

Remote sensing-based assessment of mangrove ecosystems in the Gulf Cooperation Council countries: a systematic review - Marcela Rondon; Ewane Basil Ewane; Meshal M. Abdullah; Michael S. Watt; Austin Blanton; Ammar Abulibdeh; John A. Burt; Kerrylee Rogers; Tarig Ali; Ruth Reef; Rabi Mohtar; Frida Sidik; et al. (Frontiers in Marine Science, 2023)
Mangrove forests in the Gulf Cooperation Council (GCC) countries are facing multiple threats from natural and anthropogenic-driven land use change stressors, contributing to altered ecosystem conditions. Remote sensing tools can be used to monitor mangroves, measure mangrove forest-and-tree-level attributes and vegetation indices at different spatial and temporal scales that allow a detailed and comprehensive understanding of these important ecosystems. Using a systematic literature approach, we reviewed 58 remote sensing-based mangrove assessment articles published from 2010 through 2022. The main objectives of the study were to examine the extent of mangrove distribution and cover, and the remotely sensed data sources used to assess mangrove forest/tree attributes. The key importance of and threats to mangroves that were specific to the region were also examined. Mangrove distribution and cover were mainly estimated from satellite images (75.2%), using NDVI (Normalized Difference Vegetation Index) derived from Landsat (73.3%), IKONOS (15%), Sentinel (11.7%), WorldView (10%), QuickBird (8.3%), SPOT-5 (6.7%), MODIS (5%) and others (5%) such as PlanetScope. Remotely sensed data from aerial photographs/images (6.7%), LiDAR (Light Detection and Ranging) (5%) and UAV (Unmanned Aerial Vehicles)/Drones (3.3%) were the least used. Mangrove cover decreased in Saudi Arabia, Oman, Bahrain, and Kuwait between 1996 and 2020. However, mangrove cover increased appreciably in Qatar and remained relatively stable for the United Arab Emirates (UAE) over the same period, which was attributed to government conservation initiatives toward expanding mangrove afforestation and restoration through direct seeding and seedling planting. The reported country-level mangrove distribution and cover change results varied between studies due to the lack of a standardized methodology, differences in satellite imagery resolution and classification approaches used. There is a need for UAV-LiDAR ground truthing to validate country-and-local-level satellite data. Urban development-driven coastal land reclamation and pollution, climate change-driven temperature and sea level rise, drought and hypersalinity from extreme evaporation are serious threats to mangrove ecosystems. Thus, we encourage the prioritization of mangrove conservation and restoration schemes to support the achievement of related UN Sustainable Development Goals (13 climate action, 14 life below water, and 15 life on land) in the GCC countries.

Optimization of Survey Area for Auriferous-Sulphide Mineralization Using Integrated Geophysical Study: A Case Study from Gani-Kalva Fault Zone, Cuddapah Basin, India - D. Vijayakumar; M. Mohan Babu; G. Srinivasa Rao; G. Rohit; D. G. Madhusudhan (Pure and Applied Geophysics, 2023)

Exogenous delivery of dsRNA for management of mungbean yellow mosaic virus on blackgram - K. Kamesh Krishnamoorthy; V. G. Malathi; P. Renukadevi; S. Mohan Kumar; M. Raveendran; M. Sudha; N. Manivannan; G. Karthikeyan (Planta, 2023)

Pilot-scale aerobic granular sludge reactors with granular activated carbon for effective nitrogen and phosphorus removal from domestic wastewater - Y.V. Nancharaiah; M. Sarvajith; T.V. Krishna Mohan (Science of The Total Environment, 2023)

Analyzing the streamflow teleconnections of greater Pampa basin, Kerala, India using wavelet coherence - Meera G. Mohan; S. Fathima; S. Adarsh; Nimisha Baiju; G.R. Arathy Nair; S. Meenakshi; M. Soumya Krishnan (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Experimental safety testing confirms that the NSAID nimesulide is toxic to Gyps vultures in India - Karikalan Mathesh; Kesavan Manickam; John W. Mallord; K. Mahendran; Asok Kumar M.; Debasish Saikia; Chandra Mohan S.; Beena V.; Sree Lakshmi P.; Nikita Prakash; Rohan Shringarpure; Abhijit M. Pawde; et al. (Environmental Toxicology and Pharmacology, 2023)

Guillain Barre Syndrome as a Complication of Infections Including COVID-19: a Review - Shruti V. Kurup; Pratiksha M. Patil; Sonam S. Atkari; Sakshi R. Divate; Baban S. Thawkar; Mohan K. Kale (Current Pharmacology Reports, 2023)

Petrogenesis of metavolcanics and detrital zircon geochronology of the Mesoarchean western Iron Ore Group supracrustals, Singhbhum Craton (India): Evidence for an intracontinental extension setting - Ajay Dev Asokan; M. Ram Mohan; Satya Narayana Mahapatro; Ravi Shankar; K. Rasheed (Precambrian Research, 2023)

Revealing Adaptability of Sugar Beet (Beta vulgaris) Genotypes Through Environmental Interaction (GEI) connecting Variations in Tuber Yield - M. Shanmuganathan; D. Kumaresan; S. Geetha; M. Dhasarathan; M. Jayaramachandran; R. Sudhagar; T. Selvakumar; L. Chitra; S. Mohan; A. Gurusamy; K. Iyanar (Agricultural Research, 2023)

Highly sensitive near room temperature operable NO2 gas-sensor for enhanced selectivity via nanoporous CuO@ZnO heterostructures - A. Govind; P. Bharathi; M. Krishna Mohan; J. Archana; S. Harish; M. Navaneethan (Journal of Environmental Chemical Engineering, 2023)

Occurrence and toxicity of cyanobacterium Microcystis aeruginosa in freshwater ecosystems of the Indian subcontinent: a review - Renju Mohan; M. A. Anjaly; Lathika Cicily Thomas; K. B. Padmakumar (Energy, Ecology and Environment, 2023)

Special Issue: Geostatistics Toronto 2021 - Sebastian Avalos; Julian M. Ortiz; R. Mohan Srivastava (Mathematical Geosciences, 2023)

Assessing groundwater recharge rates, water quality changes, and agricultural impacts of large-scale water recycling - Kavita Verma; Manjari Manisha; R.M. Santrupt; T.P. Anirudha; Shubham Goswami; M. Sekhar; N. Ramesh; Mohan Kumar M S; H.N. Chanakya; Lakshminarayana Rao (Science of The Total Environment, 2023)

Bioaugmentation-assisted bioremediation and biodegradation mechanisms for PCB in contaminated environments: A review on sustainable clean-up technologies - Auwalu Hassan; Fauziah S. Hamid; Agamuthu Pariatamby; Nurul Shamsinah M. Suhaimi; Noor Maiza binti M. Razali; Kimberly N.H. Ling; Priya Mohan (Journal of Environmental Chemical Engineering, 2023)

Investigating underground water salinity in east coastline of Tamil Nadu, India and improving its quality through solar assisted desalination - V. Kanchana; P. Manoj Kumar; P. Suresh Kumar; I. Kathir; R. Thirumalai; D. Priya; R. Puviarasi; M. Mohan Prasad (Urban Climate, 2023)

Assessment of underground water quality and water quality index across the Noyyal River basin of Tirupur District in South India - N. Krishnamoorthy; R. Thirumalai; M. Lenin Sundar; M. Anusuya; P. Manoj Kumar; E. Hemalatha; M. Mohan Prasad; Neha Munjal (Urban Climate, 2023)

Agulhas leakage extension and its influences on South Atlantic surface water hydrography during the Pleistocene - B. Nirmal; K. Mohan; Aradhna Tripati; Beth A. Christensen; P. Graham Mortyn; David De Vleeschouwer; M. Prakasam; K. Saravanan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Sharp-edged pencil type ZnO flowers and BiOI flakes combined with carbon nanofibers as heterostructured hybrid photocatalysts for the removal of hazardous pollutants from contaminated water - N. Ramesh Reddy; A. Sai Kumar; P. Mohan Reddy; Dhananjaya Merum; Raghava Reddy Kakarla; Jae Hak Jung; Sang Woo Joo; Tejraj M. Aminabhavi (Journal of Environmental Management, 2023)

Spatiotemporal evolution of sea ice and its teleconnections with large-scale climate indices over Antarctica - M. Swathi; Avinash Kumar; Rahul Mohan (Marine Pollution Bulletin, 2023)

Infestation, distribution and diversity indices of bruchid species on edible stored pulses in India - Revanasidda Aidbhavi; Murali Mohan K; Soren K R; Sanjay M Bandi; Ranjitha M R; Kodandaram M H (Journal of Stored Products Research, 2023)

Efficient aqueous molybdenum removal using commercial Douglas fir biochar and its iron oxide hybrids - Naba Krishna Das; Chanaka M. Navarathna; Jacinta Alchouron; Beatrice Arwenyo; Sharifur Rahman; Brooke Hoffman; Khiara Lee; Sean Stokes; Renel Anderson; Felio Perez; Dinesh Mohan; Charles U. Pittman; et al. (Journal of Hazardous Materials, 2023)

Petrogenesis of Meso-Neoarchean granitoids from the Chitradurga Greenstone Belt: Implications on crustal growth and reworking of the Dharwar Craton, southern India - M. Ram Mohan; Neal J. McNaughton; D. Srinivasa Sarma; M. Rajamanickam; Ian R. Fletcher; Simon A. Wilde; Birger Rasmussen; Bryan Krapež; S. Balakrishnan (Journal of Asian Earth Sciences, 2023)

Identification of genomic regions governing moisture and heat stress tolerance employing association mapping in rice (Oryza sativa L.) - Madhavilatha Kommana; D. Mohan Reddy; K. Amarnath; M. Vinod Kumar Naik; D. M. Withanawasam; Reddyyamini Bommisetty; K. Maneesha; M. Bhargavi; Aparna Eragam; B. V. Bhaskara Reddy; P. Sudhakar; Lalam Krishna; et al. (Molecular Biology Reports, 2023)

Antibacterial natural products from microbial and fungal sources: a decade of advances - Sangeetha Mohan; M. S. Ajay Krishna; Manasa Chandramouli; Rangappa S. Keri; Siddappa A. Patil; Srikantamurthy Ningaiah; Sasidhar B. Somappa (Molecular Diversity, 2023)

Novel rhombus Co3O4-nanocapsule CuO heterohybrids for efficient photocatalytic water splitting and electrochemical energy storage applications - N. Ramesh Reddy; A. Sai Kumar; P. Mohan Reddy; Raghava Reddy Kakarla; Sang Woo Joo; Tejraj M. Aminabhavi (Journal of Environmental Management, 2023)

Different Roles of Beclin1 in the Interaction Between Glia and Neurons after Exposure to Morphine and the HIV- Trans-Activator of Transcription (Tat) Protein - Jessica Lapierre; Mohan K. M. Karuppan; Marissa Perry; Myosotys Rodriguez; Nazira El-Hage (Journal of Neuroimmune Pharmacology, 2022)

Gut–Brain Axis, Neurodegeneration and Mental Health: A Personalized Medicine Perspective - Alisha Chunduri; S. Deepak Mohan Reddy; M. Jahanavi; C. Nagendranatha Reddy (Indian Journal of Microbiology, 2022)

Soil carbon pools under rubber (Hevea brasiliensis) based agroforestry systems in South India - Phebe Joseph; M. D. Jessy; Mahesh Mohan (Agroforestry Systems, 2022)

DNA Barcode and Phylogenetic Analysis of Serranidae Fish (subfamily: Epinephelinae) From a Tropical Island Ecosystem of the Indian Ocean - V. Sachithanandam; N. Muruganandam; D.S. Sayi; Trivesh S. Mayekar; P. M. Mohan (Thalassas: An International Journal of Marine Sciences, 2022)

Heterogeneous catalyst SiO2–LaCl3·7H2O: characterization and microwave-assisted green synthesis of α-aminophosphonates and their antimicrobial activity - S. K. Thaslim Basha; Reddi Mohan Naidu Kalla; M. Varalakshmi; H. Sudhamani; Rama Moorthy Appa; Sung Chul Hong; Chamarthi Naga Raju (Molecular Diversity, 2022)

Pyramiding of drought adaptive traits and development of doubled haploids in the traits pyramided rice (Oryza sativa L.) - Kavita Kotyal; Chaitanya Ghalagi; M. R. Namratha; Basavaiah Mohan Raju (Plant Physiology Reports, 2022)

Serum glucose-regulated protein 78 (GRP78) levels in COVID-19-associated mucormycosis: results of a case–control study - Valliappan Muthu; Manpreet Dhaliwal; Arunima Sharma; Divya Nair; H. Mohan Kumar; Shivaprakash M. Rudramurthy; Inderpaul Singh Sehgal; Hansraj Choudhary; Naresh Panda; Arunaloke Chakrabarti; Ritesh Agarwal (Mycopathologia, 2022)

Pathogenesis and management of traumatic brain injury (TBI): role of neuroinflammation and anti-inflammatory drugs - Sunishtha Kalra; Rohit Malik; Govind Singh; Saurabh Bhatia; Ahmed Al-Harrasi; Syam Mohan; Mohammed Albratty; Ali Albarrati; Murtaza M. Tambuwala (Inflammopharmacology, 2022)
Traumatic brain injury (TBI) is an important global health concern that represents a leading cause of death and disability. It occurs due to direct impact or hit on the head caused by factors such as motor vehicles, crushes, and assaults. During the past decade, an abundance of new evidence highlighted the importance of inflammation in the secondary damage response that contributes to neurodegenerative and neurological deficits after TBI. It results in disruption of the blood–brain barrier (BBB) and initiates the release of macrophages, neutrophils, and lymphocytes at the injury site. A growing number of researchers have discovered various signalling pathways associated with the initiation and progression of inflammation. Targeting different signalling pathways (NF-κB, JAK/STAT, MAPKs, PI3K/Akt/mTOR, GSK-3, Nrf2, RhoGTPase, TGF-β1, and NLRP3) helps in the development of novel anti-inflammatory drugs in the management of TBI. Several synthetic and herbal drugs with both anti-inflammatory and neuroprotective potential showed effective results. This review summarizes different signalling pathways, associated pathologies, inflammatory mediators, pharmacological potential, current status, and challenges with anti-inflammatory drugs.

Neoarchean crust–mantle interactions from the Eastern Dharwar Craton: Insights from mineral chemistry of the Nizamabad granites, southern India - Balaboina Vikram Raju; Ajay Dev Asokan; Rohit Pandey; Arathi G Panicker; M Ram Mohan (Journal of Earth System Science, 2022)

Scientists Against War: A Plea to World Leaders for Better Governance - Seithikurippu R. Pandi-Perumal; Velayudhan Mohan Kumar; Namasivayam Ganesh Pandian; Joop T. de Jong; Sudalaikannu Andiappan; Alexandru Corlateanu; Arehally Marappa Mahalaksmi; Saravana Babu Chidambaram; Ramasamy Rajesh Kumar; Chellamuthu Ramasubramanian; Sudhakar Sivasubramaniam; Alvhild Alette Bjørkum; et al. (Sleep and Vigilance, 2022)

Feasibility of bioleaching integrated with a chemical oxidation process for improved leaching of valuable metals from refinery spent hydroprocessing catalyst - Ashish Pathak; Mohan S. Rana; Hanadi Al-Sheeha; Rajasekaran Navvmani; Hanan M. Al-Enezi; Sakeena Al-Sairafi; Jayshree Mishra (Environmental Science and Pollution Research, 2022)

Nickel-mediated lead dynamics and their interactive effect on lead partitioning and phytoremediation indices in spinach - Mohan Lal Dotaniya; Jaypal Singh Pipalde; Ramesh Chandra Jain; Rajendiran Selladurai; Subhash Chandra Gupta; Madhav Das Vyas; M Vassanda Coumar; Sonalika Sahoo; Jayanta Kumar Saha; Ajay Kumar (Environmental Monitoring and Assessment, 2022)

Pathogenicity of Beauveria bassiana and Metarhizium anisopliae on Aak grasshopper, Poekilocerus pictus Fabr. (Orthoptera: Acrididea) - Ramanujam B; Kandan A; Poornesha B; Shylesha AN; Gracy Gandhi; Mohan M (International Journal of Tropical Insect Science, 2022)

Performance evaluation of geospatially assisted reference evapotranspiration models - Dinagarapandi Pandi; Kothadaramanan Saravanan; Mohan Kuppusamy; M Birasnav (Arabian Journal of Geosciences, 2022)

Impact of water deficit stress on traits influencing the drought tolerance and yield of maize (Zea mays L.) genotypes - P. Sathish; M. Vanaja; N. Jyothi Lakshmi; B. Sarkar; G. Vijay Kumar; P. Vagheera; C. H. Mohan; M. Maheswari (Plant Physiology Reports, 2022)

Consumption of reused vegetable oil intensifies BRCA1 mutations - Peramaiyan Rajendran; Abdullah M. Alzahrani; Thamaraiselvan Rengarajan; Vishnu Priya Veeraraghavan; Surapaneni Krishna Mohan (Critical Reviews in Food Science and Nutrition, 2022)

Vertical distribution of PM10 and PM2.5 emission sources and chemical composition during winter period in Delhi city - R. Shanmuga Priyan; Anju Elizbath Peter; Jyothi S. Menon; Mohan George; S. M. Shiva Nagendra; Mukesh Khare (Air Quality, Atmosphere & Health, 2022)

Unveiling tree diversity and carbon density of homegarden in the Thodupuzha urban region of Kerala, India: a contribution towards urban sustainability - Babu Padmakumar; N. P. Sreekanth; V. Shanthiprabha; Joby Paul; K. Sreedharan; Toms Augustine; K. K. Jayasooryan; M. Rameshan; V. Arunbabu; Mahesh Mohan; V. P. Sylas; E. V. Ramasamy; et al. (Tropical Ecology, 2021)

Biomass and vegetation carbon stock in mangrove forests of the Andaman Islands, India - P. Ragavan; Sanjeev Kumar; K. Kathiresan; P. M. Mohan; R. S. C. Jayaraj; K. Ravichandaran; T. S. Rana (Hydrobiologia, 2021)

Ensuring the adaptive potential of Coastal wetlands of India- the need of the hour for sustainable management - P. Ragavan; K. Kathiresan; P. M. Mohan; K. Ravichandran; R. S. C. Jayaraj; T. S. Rana (Wetlands Ecology and Management, 2021)

Multi-drug resistant (MDR), extended spectrum beta-lactamase (ESBL) producing and carbapenem resistant Escherichia coli in rescued Sloth bears (Melursus ursinus), India - O. R. VinodhKumar; M. Karikalan; S. Ilayaraja; Arun A. Sha; B. R. Singh; D. K. Sinha; S. Chandra Mohan; B. S. Pruthvishree; A. M. Pawde; A. K. Sharma (Veterinary Research Communications, 2021)

Trace gases and PM2.5-bound metal abundance over a tropical urban environment, South India - Abdul Shukkur M; Gopikrishna V.G; Vishnu N.G; Mahesh Mohan (Journal of Atmospheric Chemistry, 2021)

Ontogenetic Patterns of Elemental Tracers in the Vertebrae Cartilage of Coastal and Oceanic Sharks - Mariah C. Livernois; John A. Mohan; Thomas C. TinHan; Travis M. Richards; Brett J. Falterman; Nathan R. Miller; R. J. David Wells (Frontiers in Marine Science, 2021)
As predators, coastal and oceanic sharks play critical roles in shaping ecosystem structure and function, but most shark species are highly susceptible to population declines. Effective management of vulnerable shark populations requires knowledge of species-specific movement and habitat use patterns. Since sharks are often highly mobile and long-lived, tracking their habitat use patterns over large spatiotemporal scales is challenging. However, the analysis of elemental tracers in vertebral cartilage can describe a continuous record of the life history of an individual from birth to death. This study examined trace elements (Li, Mg, Mn, Zn, Sr, and Ba) along vertebral transects of five shark species with unique life histories. From most freshwater-associated to most oceanic, these species include Bull Sharks ( Carcharhinus leucas ), Bonnethead Sharks ( Sphyrna tiburo ), Blacktip Sharks ( Carcharhinus limbatus ), Spinner Sharks ( Carcharhinus brevipinna ), and Shortfin Mako Sharks ( Isurus oxyrinchus ). Element concentrations were compared across life stages (young-of-the-year, early juvenile, late juvenile, and adult) to infer species-specific ontogenetic patterns of habitat use and movement. Many of the observed elemental patterns could be explained by known life history traits: C. leucas exhibited clear ontogenetic changes in elemental composition matching expected changes in their use of freshwater habitats over time. S. tiburo elemental composition did not differ across ontogeny, suggesting residence in estuarine/coastal regions. The patterns of elemental composition were strikingly similar between C. brevipinna and C. limbatus , suggesting they co-occur in similar habitats across ontogeny. I. oxyrinchus elemental composition was stable over time, but some ontogenetic shifts occurred that may be due to changes in migration patterns with maturation. The results presented in this study enhance our understanding of the habitat use and movement patterns of coastal and oceanic sharks, and highlights the applicability of vertebral chemistry as a tool for characterizing shark life history traits.

Protective effect of (+)–catechin against lipopolysaccharide-induced inflammatory response in RAW 264.7 cells through downregulation of NF-κB and p38 MAPK - M. A. Sunil; V. S. Sunitha; Prasanthkumar Santhakumaran; Mohind C. Mohan; Midhun Sebastian Jose; E. K. Radhakrishnan; Jyothis Mathew (Inflammopharmacology, 2021)

Green mussel (Perna viridis L.) farming in India: an analysis of major growth milestones, recent decline due to disease incidence, and prospects for revival - Shinoj Parappurathu; N. K. Sanil; P. K. Asokan; S. R. Krupesha Sharma; M. A. Pradeep; Shelton Padua; Suja Gangadharan; Gishnu Mohan; Prasanna Kumar Patil (Aquaculture International, 2021)

Evaluation of Dosing Strategies of N-acetylcysteine for Acetaminophen Toxicity in Patients Greater than 100 Kilograms: Should the Dosage Cap Be Used? - Regan A. Baum; Jordan A. Woolum; Abby M. Bailey; Molly M. Howell; Kyle A. Weant; LeeAnn Geraghty; Sanjay Mohan; Ashley N. Webb; Mark K. Su; Peter Akpunonu; Adam J. Dugan; Leanne Atchison; et al. (Journal of Medical Toxicology, 2021)

Litter degradation in evergreen forests of southern Western Ghats - M. P. Krishna; V. G. Gopikrishna; Aswathy K. Vijayan; S. Arun Sasi; Mahesh Mohan (Tropical Ecology, 2021)

Micro-array Analysis of Cold Tolerant Tomato Expressing Nicotiana tabacum Osmotin - Vikas Yadav Patade; Atul Grover; Anukriti; Sanjay Mohan Gupta; M. Nasim (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2021)

A 12‐point checklist for surveillance of diseases of aquatic organisms: a novel approach to assist multidisciplinary teams in developing countries - Melba G. Bondad‐Reantaso; Nihad Fejzic; Brett MacKinnon; David Huchzermeyer; Sabina Seric‐Haracic; Fernando O. Mardones; Chadag Vishnumurthy Mohan; Nick Taylor; Mona Dverdal Jansen; Saraya Tavornpanich; Bin Hao; Jie Huang; et al. (Reviews in Aquaculture, 2021)
A 12‐point checklist in the design and practical application of active surveillance of diseases in aquatic organisms (farmed and wild) has been developed to serve as a methodological approach and guidance for a multidisciplinary team particularly in countries where surveillance expertise is limited. The checklist is based on a review of available main aquatic surveillance references and scientific literature and was further developed based on the outcomes of several aquaculture biosecurity project‐related workshops hosted by the Food and Agriculture Organization of the United Nations. The checklist includes the following: (1) scenario setting; (2) defining surveillance objective; (3) defining the populations; (4) disease clustering; (5) case definition; (6) diagnostic testing; (7) study design and sampling; (8) data collection and management; (9) data analysis; (10) validation and quality assurance; (11) human and financial resources and logistics requirements; and (12) surveillance in the bigger picture. For a multidisciplinary approach to disease control, knowledge of fish biology, aquaculture systems and many aspects of aquaculture health management are required. Surveillance needs significant financial investment and must be supported by adequate diagnostic capability, information system management, legal framework and communication networks, with transparent reporting mechanisms to allow rapid disease response for serious diseases of aquatic organisms. It is a stepwise and pragmatic approach that offers a good starting point for addressing disease issues especially in developing countries. It can be used as a model to build targeted surveillance competency and a basic reference when implementing a surveillance programme or improving existing programmes.

Multi-year characterization of aerosol black carbon concentrations over a semiarid tropical site Udaipur - Brij Mohan Vyas; Mukunda M Gogoi; Subin Jose (Environmental Science and Pollution Research, 2021)

A novel barcode system for rapid identification of rice (Oryza sativa L.) varieties using agro-morphological descriptors and molecular markers - M. Bhargavi; K. Maneesha; D. M. Withanawasam; Kavitha R. Aratikatla; S. Himabindu; M. Prashanth; P. Shanthi; Madhavi L. Kommana; D. Mohan Reddy; B. Ravindra Reddy; Lakshminarayana R. Vemireddy (Molecular Biology Reports, 2021)

Tilletia indica: biology, variability, detection, genomics and future perspective - Malkhan Singh Gurjar; Haritha Mohan M; Jagmohan Singh; Mahender Singh Saharan; Rashmi Aggarwal (Indian Phytopathology, 2021)

Identification and characterization of a novel long juvenile resource AGS 25 - Sanjay Gupta; Giriraj Kumawat; Soniya Yadav; Rachana Tripathi; Nisha Agrawal; Shivakumar Maranna; Gyanesh K. Satpute; Gireesh Channappa; Mamta Arya; Sayed M. Husain; Virender S. Bhatia; Nanita Devi; et al. (Genetic Resources and Crop Evolution, 2021)

Evaluation of Potentiality of Different Adjuvants for Date Palm Pollination and Fruit Set - Kapil Mohan Sharma; C. M. Muralidharan; D. A. Baidiyavadra; Kirti Bardhan; C. N. Panchal (Sugar Tech, 2021)

Thymosin β4 dynamics during chicken enteroid development - Mohan Acharya; Rohana Liyanage; Anamika Gupta; Komala Arsi; Ann M. Donoghue; Jackson O. Lay; Narayan C. Rath (Molecular and Cellular Biochemistry, 2021)
The sheared avian intestinal villus-crypts exhibit high tendency to self-repair and develop enteroids in culture. Presuming that this transition process involves differential biomolecular changes, we employed matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF–MS) to find whether there were differences in the spectral profiles of sheared villi versus the enteroids, assessed in the mass range of 2–18 kDa. The results showed substantial differences in the intensities of the spectral peaks, one particularly corresponding to the mass of 4963 Da, which was significantly low in the sheared villus-crypts compared with the enteroids. Based on our previous results with other avian tissues and further molecular characterization by LC-ESI-IT-TOF–MS, and multiple reaction monitoring (MRM), the peak was identified to be thymosin β4 (Tβ4), a ubiquitously occurring regulatory peptide implicated in wound healing process. The identity of the peptide was further confirmed by immunohistochemistry which showed it to be present in a very low levels in the sheared villi but replete in the enteroids. Since Tβ4 sequesters G-actin preventing its polymerization to F-actin, we compared the changes in F-actin by its immunohistochemical localization that showed no significant differences between the sheared villi and enteroids. We propose that depletion of Tβ4 likely precedes villous reparation process. The possible mechanism for the differences in Tβ4 profile in relation to the healing of the villus-crypts to developing enteroids is discussed.

Translating a Global Emission-Reduction Framework for Subnational Climate Action: A Case Study from the State of Georgia - Marilyn A. Brown; Blair Beasley; Fikret Atalay; Kim M. Cobb; Puneet Dwiveldi; Jeffrey Hubbs; David M. Iwaniek; Sudhagar Mani; Daniel Matisoff; Jaqueline E. Mohan; Jeffrey Mullen; Michael Oxman; et al. (Environmental Management, 2021)
Subnational entities are recognizing the need to systematically examine options for reducing their carbon footprints. However, few robust and comprehensive analyses are available that lay out how US states and regions can most effectively contribute. This paper describes an approach developed for Georgia—a state in the southeastern United States called “Drawdown Georgia”, our research involves (1) understanding Georgia’s baseline carbon footprint and trends, (2) identifying the universe of Georgia-specific carbon-reduction solutions that could be impactful by 2030, (3) estimating the greenhouse gas reduction potential of these high-impact 2030 solutions for Georgia, and (4) estimating associated costs and benefits while also considering how the solutions might impact societal priorities, such as economic development opportunities, public health, environmental benefits, and equity. We began by examining the global solutions identified by Project Drawdown. The resulting 20 high-impact 2030 solutions provide a strategy for reducing Georgia’s carbon footprint in the next decade using market-ready technologies and practices and including negative emission solutions. This paper describes our systematic and replicable process and ends with a discussion of its strengths, weaknesses, and planned future research.

Pistillate Receptivity of Date Palm (Phoenix dactylifera L.) cv. Barhee - C. M. Muralidharan; C. N. Panchal; D. A. Baidiyavadra; Kapil Mohan Sharma; Piyush Verma (Sugar Tech, 2020)

Understanding stable isotope systematics of salinity affected groundwater in Mewat, Haryana, India - Gopal Krishan; N C Ghosh; C P Kumar; Lalit Mohan Sharma; Brijesh Yadav; M L Kansal; Surjeet Singh; S K Verma; Gokul Prasad (Journal of Earth System Science, 2020)

Observational aspects of tropical mesoscale convective systems over southeast India - A Madhulatha; M Rajeevan; T S Mohan; S B Thampi (Journal of Earth System Science, 2020)

Vertical distributions of the microscopic morphological characteristics and elemental composition of aerosols over India - Mukunda M. Gogoi; Roseline C. Thakur; Sahina Gazi; Vijayakumar S. Nair; Rahul Mohan; S. Suresh Babu (Journal of Atmospheric Chemistry, 2020)

Synoptic flow patterns and large-scale characteristics of flash flood-producing rainstorms over northeast Bangladesh - Mohan K. Das; A. K. M. Saiful Islam; Samarendra Karmakar; Md. Jamal Uddin Khan; Khaled Mohammed; G. M. Tarekul Islam; Sujit Kumar Bala; Thomas M. Hopson (Meteorology and Atmospheric Physics, 2020)

Future changes in meteorological drought characteristics over Bangladesh projected by the CMIP5 multi-model ensemble - Jamal Uddin Khan; A. K. M. Saiful Islam; Mohan K. Das; Khaled Mohammed; Sujit Kumar Bala; G. M. Tarekul Islam (Climatic Change, 2020)

Mercury in the sediments of freshwater lakes in Ny-Ålesund, Arctic - V. G. Gopikrishna; V. M. Kannan; M. B. Binish; M. Abdul Shukkur; K. P. Krishnan; Mahesh Mohan (Environmental Monitoring and Assessment, 2020)

The mechanisms of biochar interactions with microorganisms in soil - Andrey V. Gorovtsov; Tatiana M. Minkina; Saglara S. Mandzhieva; Leonid V. Perelomov; Gerhard Soja; Inna V. Zamulina; Vishnu D. Rajput; Svetlana N. Sushkova; Dinesh Mohan; Jun Yao (Environmental Geochemistry and Health, 2020)

Perchlorate contamination of drinking water sources in Kerala, South India, and its degradation using advanced chemical treatment - M. R. Sijimol; C. T. Aravindakumar; P. R. Manoj; D. Dineep; K. K. Nejumal; Mahesh Mohan (Energy, Ecology and Environment, 2020)

A review of inclusive business models and their application in aquaculture development - Alexander M. Kaminski; Froukje Kruijssen; Steven M. Cole; Malcolm C.M. Beveridge; Claire Dawson; Chadag V. Mohan; Sharon Suri; Manjurul Karim; Oai Li Chen; Michael J. Phillips; William Downing; Fred Weirowski; et al. (Reviews in Aquaculture, 2020)
For aquaculture to continue along its current growth trajectory and contribute towards achieving the Sustainable Development Goals, value chains must become more inclusive. Smallholders and other local value chain actors are often constrained by circumstances and market failures in the global aquaculture industry. Integrating these actors into aquaculture value chains through inclusive business models (IBMs) is often touted as a solution to sustainable and ethical trade and business that can generate development outcomes. We reviewed 36 papers under seven business models commonly used in agriculture development to assess their application in aquaculture value chains in lower‐income countries. A global value chain (GVC) analysis is used to unpack the economic and social upgrading objectives of the different IBMs, as well as the types of relational coordination used between actors in the chain to achieve development outcomes. The extent to which these IBMs helped poor actors overcome certain barriers is evaluated with a focus on how they may ensure or be a risk to inclusiveness through the relations and upgrading opportunities evident in their make‐up. The analysis found that the majority of the models focused on economic upgrading over social upgrading. Providing opportunities for the latter is key to achieving the inclusive objectives of IBMs. Greater horizontal coordination between actors can create further opportunities for economic upgrading established under vertical coordination with other nodes upstream and downstream in a value chain. There is a need to further contextualize these models to aquaculture systems and develop clear indicators of inclusiveness.

Variations in extreme temperature and precipitation for a Caribbean island: Barbados (1969–2017) - Shridevi Mohan; Ricardo M. Clarke; Xsitaaz T. Chadee (Theoretical and Applied Climatology, 2020)

Correction to: Prevalence and correlates of household food insecurity in Delhi and Chennai, India - Garima Rautela; Mohammed K. Ali; Dorairaj Prabhakaran; K.M. Venkat Narayan; Nikhil Tandon; Viswanathan Mohan; Lindsay M. Jaacks (Food Security, 2020)

Prevalence and correlates of household food insecurity in Delhi and Chennai, India - Garima Rautela; Mohammed K. Ali; Dorairaj Prabhakaran; K.M. Venkat Narayan; Nikhil Tandon; Viswanathan Mohan; Lindsay M. Jaacks (Food Security, 2020)

Multifractal description of streamflow and suspended sediment concentration data from Indian river basins - S. Adarsh; Drisya S. Dharan; A. R. Nandhu; B. Anand Vishnu; Vysakh K. Mohan; M. Wątorek (Acta Geophysica, 2020)

Oceanographic Structure and Light Levels Drive Patterns of Sound Scattering Layers in a Low-Latitude Oceanic System - Kevin M. Boswell; Marta D’Elia; Matthew W. Johnston; John A. Mohan; Joseph D. Warren; R. J. David Wells; Tracey T. Sutton (Frontiers in Marine Science, 2020)

Integration of soil moisture as an auxiliary parameter for the anchor pixel selection process in SEBAL using Landsat 8 and Sentinel - 1A images - M M Prakash Mohan; K Rajitha; Murari R R Varma (International Journal of Remote Sensing, 2020)

Rare Earth Elements in Andaman Island Surface Seawater: Geochemical Tracers for the Monsoon? - Ed C. Hathorne; Martin Frank; P. M. Mohan (Frontiers in Marine Science, 2020)

Adaptive Neuro-Fuzzy Inference System-Based Exploration of the Interrelationships of 25-Hydroxyvitamin D, Calcium, Phosphorus with Parathyroid Hormone Production - Iyyapu Krishna Mohan; Siraj Ahmed Khan; D. Shiva Krishna; M. Vijaya Bhaskar; K. S. S. Sai Baba; Tajamul Hussain; Salman A. Alrokayan; Shaik Mohammad Naushad (Indian Journal of Clinical Biochemistry, 2020)

On the relationships between plant species richness and the environment: a case study in Eastern Ghats, India - Rajendra Mohan Panda; Mukunda Dev Behera; Partha Sarathi Roy; Reshma M Ramachandran (Environmental Monitoring and Assessment, 2019)

Terminalia arjuna extract and arjunic acid mitigate cobalt chloride–induced hypoxia stress–mediated apoptosis in H9c2 cells - T. Mohan Manu; T. Anand; M. D. Pandareesh; P. Bhuvanesh Kumar; Farhath Khanum (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Regression-Based Integrated Bi-sensor SAR Data Model to Estimate Forest Carbon Stock - Suman Sinha; A. Santra; A. K. Das; L. K. Sharma; Shiv Mohan; M. S. Nathawat; S. Santra Mitra; C. Jeganathan (Journal of the Indian Society of Remote Sensing, 2019)

Molecular characterization of pea DNA gyrase-A reveals dual localization of protein in plastid and mitochondria - Malireddy K. Reddy; V. Mohan M. Achary; Badri N. Singh; Mrinalini Manna; Vijay Sheri; Varakumar Panditi; Donald James; Dhirendra Fartyal; Babu Ram; Tanushri Kaul (Journal of Plant Biochemistry and Biotechnology, 2019)

Management of candidaemia with reference to the European confederation of medical mycology quality indicators - Sophia Nemer; Toufeeq Imtiaz; Mohan Varikkara; Andrew Collier; Abhijit M. Bal (Infectious Diseases, 2019)

Recombinant Partial Conglutinin of Buffalo and Nilgai In Vitro Can Mimic the Functions of Native Conglutinin In Vivo - D. Ramesh; S. Chandra Mohan; Mohini Saini; Sasmita Barik; M. Shynu; Asit Das; Anil Kumar Sharma; Vinod Kumar Chaturvedi; Praveen Kumar Gupta (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Differences in CAPE between wet and dry spells of the monsoon over the southeastern peninsular India - T. S. Mohan; T. N. Rao; M. Rajeevan (Meteorology and Atmospheric Physics, 2019)

Magma mixing in Neoarchean granite from Nalgonda region, Eastern Dharwar Craton, India: Morphological, mineralogical and geochemical evidences - Soumya Shukla; M Ram Mohan (Journal of Earth System Science, 2019)

Accounting tropical forest carbon stock with synergistic use of space-borne ALOS PALSAR and COSMO-Skymed SAR sensors - Suman Sinha; A. Santra; A. K. Das; L. K. Sharma; Shiv Mohan; M. S. Nathawat; S. S. Mitra; C. Jeganathan (Tropical Ecology, 2019)

Intra-line uniformity and inter-line variability of doubled haploid rice lines under different environmental conditions - Debina Sanasam; M. Udaya Kumar; N. Shivakumar; B. Mohan Raju (Plant Physiology Reports, 2019)

Integrated phosphorus management in maize–chickpea cropping system on alkaline Fluvisol - M. S. Venkatesh; K. K. Hazra; P. K. Ghosh; Mohan Singh (Nutrient Cycling in Agroecosystems, 2019)

Generalised extreme value model with cyclic covariate structure for analysis of non-stationary hydrometeorological extremes - R S Jagtap; V K Gedam; Mohan M Kale (Journal of Earth System Science, 2019)

User-Guided Segmentation of Multi-modality Medical Imaging Datasets with ITK-SNAP - Paul A. Yushkevich; Artem Pashchinskiy; Ipek Oguz; Suyash Mohan; J. Eric Schmitt; Joel M. Stein; Dženan Zukić; Jared Vicory; Matthew McCormick; Natalie Yushkevich; Nadav Schwartz; Yang Gao; et al. (Neuroinformatics, 2019)

Frequency of Heterotic Hybrids in Relation to Parental Genetic Divergence and General Combining Ability in Dolichos Bean - C. M. Keerthi; S. Ramesh; M. Byregowda; A. Mohan Rao (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Linking Habitat Use and Trophic Ecology of Spotted Seatrout (Cynoscion nebulosus) on a Restored Oyster Reef in a Subtropical Estuary - Thomas C. TinHan; John A. Mohan; Mark Dumesnil; Bryan M. DeAngelis; R. J. David Wells (Estuaries and Coasts, 2018)

Mangrove floristics of the Andaman and Nicobar Islands: critical review and current scenario - P. Ragavan; P. M. Mohan; Alok Saxena; R. S. C. Jayaraj; K. Ravichandran; Mani Saxena (Marine Biodiversity, 2018)

Mesenchymal Stem Cells of Different Origin-Seeded Bioceramic Construct in Regeneration of Bone Defect in Rabbit - Swapan Kumar Maiti; M. U. Shivakumar; Divya Mohan; Naveen Kumar; Karam Pal Singh (Tissue Engineering and Regenerative Medicine, 2018)

Inhibition of proinflammatory pathways by bioactive fraction of Tinospora cordifolia - Jenny Jacob; Bashi M. Babu; Mohind C. Mohan; A. P. Abhimannue; B. Prakash Kumar (Inflammopharmacology, 2018)

Zingiber cernuum (Zingiberaceae) essential oil as effective larvicide and oviposition deterrent on six mosquito vectors, with little non-target toxicity on four aquatic mosquito predators - Mohan Rajeswary; Marimuthu Govindarajan; Naiyf S. Alharbi; Shine Kadaikunnan; Jamal M. Khaled; Giovanni Benelli (Environmental Science and Pollution Research, 2018)

Curzerene, trans-β-elemenone, and γ-elemene as effective larvicides against Anopheles subpictus, Aedes albopictus, and Culex tritaeniorhynchus: toxicity on non-target aquatic predators - Marimuthu Govindarajan; Mohan Rajeswary; Sengamalai Senthilmurugan; Periasamy Vijayan; Naiyf S. Alharbi; Shine Kadaikunnan; Jamal M. Khaled; Giovanni Benelli (Environmental Science and Pollution Research, 2018)

Boswellia ovalifoliolata (Burseraceae) essential oil as an eco-friendly larvicide? Toxicity against six mosquito vectors of public health importance, non-target mosquito fishes, backswimmers, and water bugs - Giovanni Benelli; Mohan Rajeswary; Periasamy Vijayan; Sengamalai Senthilmurugan; Naiyf S. Alharbi; Shine Kadaikunnan; Jamal M. Khaled; Marimuthu Govindarajan (Environmental Science and Pollution Research, 2018)

Simultaneous detection and serotyping of dengue infection using single tube multiplex CDC Dengue Real-Time RT-PCR from India - Shashi Sharma; Kundan Tandel; Surabhi Danwe; Puneet Bhatt; P. K. Dash; Praveer Ranjan; K. R. Rathi; Rajiv Mohan Gupta; M. M. Parida (VirusDisease, 2018)

Direct and indirect influences of intercrops on the coconut defoliator Opisina arenosella - K. S. Shameer; M. Nasser; Chandrika Mohan; Ian C. W. Hardy (Journal of Pest Science, 2018)

Detection of Tilapia Lake Virus in Egyptian fish farms experiencing high mortalities in 2015 - P Nicholson; M A Fathi; A Fischer; C Mohan; E Schieck; N Mishra; A Heinimann; J Frey; B Wieland; J Jores (Journal of Fish Diseases, 2017)

Interaction of coeval felsic and mafic magmas from the Kanker granite, Pithora region, Bastar Craton, Central India - R Elangovan; Kumar Krishna; Neeraj Vishwakarma; K R Hari; M Ram Mohan (Journal of Earth System Science, 2017)

Influence of oceanographic conditions on abundance and distribution of post‐larval and juvenile carangid fishes in the northern Gulf of Mexico - John A. Mohan; Tracey T. Sutton; April B. Cook; Kevin M. Boswell; R. J. David Wells (Fisheries Oceanography, 2017)
Relationships between abundance of post‐larval and juvenile carangid (jacks) fishes and physical oceanographic conditions were examined in the northern Gulf of Mexico (GoM) in 2011 with high freshwater input from the Mississippi River. Generalized additive models ( GAM s) were used to explore complex relationships between carangid abundance and physical oceanographic data of sea surface temperature ( SST ), sea surface height anomaly ( SSHA ) and salinity. The five most abundant carangid species collected were: Selene setapinnis (34%); Caranx crysos (30%); Caranx hippos (10%); Chloroscombrus chrysurus (9%) and Trachurus lathami (8%). Post‐larval carangids (median standard length [ SL ] = 10 mm) were less abundant during the spring and early summer, but more abundant during the late summer and fall, suggesting summer to fall spawning for most species. Juvenile carangid (median SL = 23 mm) abundance also increased between the mid‐summer and early fall. Most species showed increased abundance at lower salinities and higher temperatures, suggesting entrainment of post‐larval fishes or feeding aggregations of juveniles at frontal convergence zones between the expansive river plume and dynamic mesoscale eddy water masses. However, responses were species‐ and life‐stage specific, which may indicate fine‐scale habitat partitioning between species. Ordination methods also revealed higher carangid abundances at lower salinities for both post‐larval and juvenile life stages, with species‐ and life‐stage specific responses to SST and SSHA , further suggesting habitat separation between species. Results indicate strong links between physical oceanographic features and carangid distributions in the dynamic northern GoM.

Litter decomposition in forest ecosystems: a review - M. P. Krishna; Mahesh Mohan (Energy, Ecology and Environment, 2017)

Perchlorate in drinking water around rocket manufacturing and testing facilities and firework manufacturing sites in Kerala, India - M. R. Sijimol; V. G. Gopikrishna; D. Dineep; Mahesh Mohan (Energy, Ecology and Environment, 2017)

Total and methyl mercury in the water, sediment, and fishes of Vembanad, a tropical backwater system in India - E. V. Ramasamy; K. K. Jayasooryan; M. S. Shylesh Chandran; Mahesh Mohan (Environmental Monitoring and Assessment, 2017)

Impacts of community-based fish culture in seasonal floodplains on income, food security and employment in Bangladesh - A. B. M. Mahfuzul Haque; Madan Mohan Dey (Food Security, 2017)

High-fructose diet is as detrimental as high-fat diet in the induction of insulin resistance and diabetes mediated by hepatic/pancreatic endoplasmic reticulum (ER) stress - M. Balakumar; L. Raji; D. Prabhu; C. Sathishkumar; P. Prabu; V. Mohan; M. Balasubramanyam (Molecular and Cellular Biochemistry, 2016)

Spectrum of DNA variants for non-syndromic deafness in a large cohort from multiple continents - Denise Yan; Demet Tekin; Guney Bademci; Joseph Foster; F. Basak Cengiz; Abhiraami Kannan-Sundhari; Shengru Guo; Rahul Mittal; Bing Zou; Mhamed Grati; Rosemary I. Kabahuma; Mohan Kameswaran; et al. (Human Genetics, 2016)

Population genomics of dengue virus serotype 4: insights into genetic structure and evolution - Vaishali P. Waman; Sunitha Manjari Kasibhatla; Mohan M. Kale; Urmila Kulkarni-Kale (Archives of Virology, 2016)

Optimization of Wastewater Anaerobic Digestion Using Mechanistic and Meta-heuristic Methods: Current Limitations and Future Opportunities - P. E. Poh; D. Gouwanda; Y. Mohan; A. A. Gopalai; H. M. Tan (Water Conservation Science and Engineering, 2016)

Occurrence of Marbled Shrimp Saron marmoratus (Olivier, 1811) (Decapoda: Caridea: Hippolytidae) in Lakshadweep Archipelago, India - Sibi Thaitharanikathil Baby; Swagat Ghosh; Gopi Mohan; Sherine Sonia Cubelio; M. Sudhakar (Proceedings of the Zoological Society, 2016)

Developing synergy regression models with space-borne ALOS PALSAR and Landsat TM sensors for retrieving tropical forest biomass - Suman Sinha; C Jeganathan; L K Sharma; M S Nathawat; Anup K Das; Shiv Mohan (Journal of Earth System Science, 2016)

Perchlorate contamination in bottled and other drinking water sources of Kerala, southwest coast of India - M. R. Sijimol; Mahesh Mohan; D. Dineep (Energy, Ecology and Environment, 2016)

Distribution, enrichment, and potential toxicity of trace metals in the surface sediments of Sundarban mangrove ecosystem, Bangladesh: a baseline study before Sundarban oil spill of December, 2014 - Alok Kumar; AL. Ramanathan; M. B. K. Prasad; Dilip Datta; Manoj Kumar; Swati Mohan Sappal (Environmental Science and Pollution Research, 2016)

Further evidence for the genetic basis of qualitative traits and their linkage relationships in dolichos bean (Lablab purpureus L.) - C. M. KEERTHI; S. RAMESH; M. BYREGOWDA; A. MOHAN RAO; B. S. RAJENDRA PRASAD; P. V. VAIJAYANTHI (Journal of Genetics, 2016)

Dose calculation, design and development of nateglinide matrix tablets using quality by design approach and its pharmacokinetic evaluation in animal model - Sudheer Betha; B. Pamula Reddy; P. V. Swamy; M. Mohan Varma; D. Basava Raju; Venkata Ramana Murthy Kolapalli (Journal of Pharmaceutical Investigation, 2015)

Diversity, distribution and vegetative structure of mangroves of the Andaman and Nicobar Islands, India - P. Ragavan; Alok Saxena; P. M. Mohan; K. Ravichandran; R. S. C. Jayaraj; S. Saravanan (Journal of Coastal Conservation, 2015)

Advancing Product Quality: a Summary of the Inaugural FDA/PQRI Conference - Lawrence X. Yu; Jeffrey Baker; Susan C. Berlam; Ashley Boam; E. J. Brandreth; Lucinda Buhse; Thomas Cosgrove; David Doleski; Lynne Ensor; Joseph Famulare; Mohan Ganapathy; Gustavo Grampp; et al. (The AAPS Journal, 2015)

Antioxidant System Against Active Oxygen Species in Cyanobacterium Aphanothece stagnina: Response to Excess Light Under Cadmium Stress - M. P. V. V. B. Singh; Sheo Mohan Prasad; Vijay Pratap Singh; Meenakshi Singh (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Real-time numerical simulation of tropical cyclone Nilam with WRF: experiments with different initial conditions, 3D-Var and Ocean Mixed Layer Model - Greeshma M. Mohan; C. V. Srinivas; C. V. Naidu; R. Baskaran; B. Venkatraman (Natural Hazards, 2015)

Isolation and Characterization of Circadian Clock Genes in the Biofuel Plant Pongamia (Millettia pinnata) - Harry P. Winarto; Lim Chee Liew; Peter M. Gresshoff; Paul T. Scott; Mohan B. Singh; Prem L. Bhalla (BioEnergy Research, 2015)

Image cytometric analysis of nuclear and chromosomal DNA contents in two cytotypes of Aloe vera (L.) Burm. f. - Bandaru V. Rao; M. Barathi; Tavva S. S. Mohan Dev; Monika Singh (The Nucleus, 2015)

Habitat use of juvenile striped bass Morone saxatilis (Actinopterygii: Moronidae) in rivers spanning a salinity gradient across a shallow wind-driven estuary - John A. Mohan; Norman M. Halden; Roger A. Rulifson (Environmental Biology of Fishes, 2015)

Effect of Ultra-High Pressure Homogenization on the Interaction Between Bovine Casein Micelles and Ritonavir - M. Corzo-Martínez; M. Mohan; J. Dunlap; F. Harte (Pharmaceutical Research, 2015)

Development of simvastatin electrospun fibers: a novel approach for sustained drug delivery - Sudheer Betha; B. Pamula Reddy; M. Mohan Varma; D. Basava Raju; Venkata Ramana Murthy Kolapalli (Journal of Pharmaceutical Investigation, 2015)

Histopathological findings on innate responses of white spot disease positive Penaeus monodon (Fabricius) under semi‐intensive culture - A K Sahoo; P C Thakur; K M Shankar; C V Mohan; S R Krupesha Sharma; F Corsin (Journal of Fish Diseases, 2015)

Overexpression of NAC gene from Lepidium latifolium L. enhances biomass, shortens life cycle and induces cold stress tolerance in tobacco: potential for engineering fourth generation biofuel crops - Atul Grover; Sadhana Singh; Pankaj Pandey; Vikas Yadav Patade; Sanjay Mohan Gupta; M. Nasim (Molecular Biology Reports, 2014)

Environmental impacts of perchlorate with special reference to fireworks—a review - M. R. Sijimol; Mahesh Mohan (Environmental Monitoring and Assessment, 2014)

Automatic classification of protein structures using physicochemical parameters - Abhilash Mohan; M. Divya Rao; Shruthi Sunderrajan; Gautam Pennathur (Interdisciplinary Sciences: Computational Life Sciences, 2014)

Mercury in the sediments of Vembanad Lake, western coast of India - Mahesh Mohan; M S Shylesh Chandran; K K Jayasooryan; E V Ramasamy (Environmental Monitoring and Assessment, 2014)

Genetics of growth habit and photoperiodic response to flowering time in dolichos bean (Lablab purpureus (L.) Sweet) - C. M. KEERTHI; S. RAMESH; M. BYREGOWDA; A. MOHAN RAO; B. S. RAJENDRA PRASAD; P. V. VAIJAYANTHI (Journal of Genetics, 2014)

Developing Marine Protected Area Networks in the Coral Triangle: Good Practices for Expanding the Coral Triangle Marine Protected Area System - Rebecca Weeks; Porfirio M. Aliño; Scott Atkinson; Pacifico Beldia; Augustine Binson; Wilfredo L. Campos; Rili Djohani; Alison L. Green; Richard Hamilton; Vera Horigue; Robecca Jumin; Kay Kalim; et al. (Coastal Management, 2014)

GSL2 over-expression confers resistance to Pectobacterium atrosepticum in potato - Sara Mohan; Sathiyamoorthy Meiyalaghan; Julie M. Latimer; Michelle L. Gatehouse; Katrina S. Monaghan; Bhanupratap R. Vanga; Andrew R. Pitman; E. Eirian Jones; Anthony J. Conner; Jeanne M. E. Jacobs (Theoretical and Applied Genetics, 2014)

Increased circulatory levels of lipopolysaccharide (LPS) and zonulin signify novel biomarkers of proinflammation in patients with type 2 diabetes - B. Jayashree; Y. S. Bibin; D. Prabhu; C. S. Shanthirani; K. Gokulakrishnan; B. S. Lakshmi; V. Mohan; M. Balasubramanyam (Molecular and Cellular Biochemistry, 2014)

Analytical solutions for transient temperature distribution in a geothermal reservoir due to cold water injection - Sayantan Ganguly; M. S. Mohan Kumar (Hydrogeology Journal, 2014)

Production and purification of a hyperthermostable chitinase from Brevibacillus formosus BISR-1 isolated from the Great Indian Desert soils - Savita Meena; Raj Kumar Gothwal; M. Krishna Mohan; Purnendu Ghosh (Extremophiles, 2014)

The N-terminal region containing the zinc finger domain of tobacco streak virus coat protein is essential for the formation of virus-like particles - Chhavi Mathur; Kalyani Mohan; T. R. Usha Rani; M. Krishna Reddy; Handanahal S. Savithri (Archives of Virology, 2014)

A synthetic chimeric peptide harboring human papillomavirus 16 cytotoxic T lymphocyte epitopes shows therapeutic potential in a murine model of cervical cancer - Chandresh Sharma; M. A. Khan; Teena Mohan; Jatin Shrinet; N. Latha; Neeta Singh (Immunologic Research, 2014)

Metal stoichiometry of isolated and arsenic substituted metallothionein: PIXE and ESI-MS study - Roobee Garla; Biraja P. Mohanty; Renuka Ganger; M. Sudarshan; Mohinder P. Bansal; Mohan L. Garg (BioMetals, 2013)

Deep transcriptome sequencing reveals the expression of key functional and regulatory genes involved in the abiotic stress signaling pathways in rice - R. C. Venu; M. V. Sreerekha; M. Sheshu Madhav; Kan Nobuta; K. Madhan Mohan; Songbiao Chen; Yulin Jia; Blake C. Meyers; Guo-Liang Wang (Journal of Plant Biology, 2013)

Elucidation of lead-induced oxidative stress in Talinum triangulare roots by analysis of antioxidant responses and DNA damage at cellular level - Abhay Kumar; M. N. V. Prasad; V. Mohan Murali Achary; Brahma B. Panda (Environmental Science and Pollution Research, 2013)

Depositional environment in and around Tamiraparani estuary, and off Tuticorin, Tamil Nadu, India: clues from grain size studies - A. Solai; M. Suresh Gandhi; K. Chandrasekaran; V. Ram Mohan (Arabian Journal of Geosciences, 2013)

Provenance and temporal variability of ice rafted debris in the Indian sector of the Southern Ocean during the last 22,000 years - M C MANOJ; MELOTH THAMBAN; A SAHANA; RAHUL MOHAN; KOTHA MAHENDER (Journal of Earth System Science, 2013)

Atmospheric deposition studies of heavy metals in Arctic by comparative analysis of lichens and cryoconite - Shiv Mohan Singh; Jagdev Sharma; Puja Gawas-Sakhalkar; Ajay K. Upadhyay; Simantini Naik; Shailesh M. Pedneker; Rasik Ravindra (Environmental Monitoring and Assessment, 2013)

Terpenoids of plant origin inhibit morphogenesis, adhesion, and biofilm formation by Candida albicans - Jayant S. Raut; Ravikumar B. Shinde; Nitin M. Chauhan; S. Mohan Karuppayil (Biofouling, 2013)

Earthworm diversity at Nilgiri biosphere reserve, Western Ghats, India - M. S. Shylesh Chandran; S. Sujatha; Mahesh Mohan; J. M. Julka; E. V. Ramasamy (Biodiversity and Conservation, 2012)

Advances in genetics and molecular breeding of three legume crops of semi-arid tropics using next-generation sequencing and high-throughput genotyping technologies - Rajeev K Varshney; Himabindu Kudapa; Manish Roorkiwal; Mahendar Thudi; Manish K Pandey; Rachit K Saxena; Siva K Chamarthi; Murali Mohan S; Nalini Mallikarjuna; Hari Upadhyaya; Pooran M Gaur; L Krishnamurthy; et al. (Journal of Biosciences, 2012)

Offshore depositional sequence of 2004 tsunami from Chennai, SE coast of India - M. P. Jonathan; S. Srinivasalu; N. Thangadurai; N. Rajeshwara-Rao; V. Ram-Mohan; T. Narmatha (Natural Hazards, 2012)

Accumulation of mercury and other heavy metals in edible fishes of Cochin backwaters, Southwest India - Mahesh Mohan; M. Deepa; E. V. Ramasamy; A. P. Thomas (Environmental Monitoring and Assessment, 2012)

Density estimation in tiger populations: combining information for strong inference - Arjun M. Gopalaswamy; J. Andrew Royle; Mohan Delampady; James D. Nichols; K. Ullas Karanth; David W. Macdonald (Ecology, 2012)
A productive way forward in studies of animal populations is to efficiently make use of all the information available, either as raw data or as published sources, on critical parameters of interest. In this study, we demonstrate two approaches to the use of multiple sources of information on a parameter of fundamental interest to ecologists: animal density. The first approach produces estimates simultaneously from two different sources of data. The second approach was developed for situations in which initial data collection and analysis are followed up by subsequent data collection and prior knowledge is updated with new data using a stepwise process. Both approaches are used to estimate density of a rare and elusive predator, the tiger, by combining photographic and fecal DNA spatial capture–recapture data. The model, which combined information, provided the most precise estimate of density (8.5 ± 1.95 tigers/100 km 2 [posterior mean ± SD]) relative to a model that utilized only one data source (photographic, 12.02 ± 3.02 tigers/100 km 2 and fecal DNA, 6.65 ± 2.37 tigers/100 km 2 ). Our study demonstrates that, by accounting for multiple sources of available information, estimates of animal density can be significantly improved.

Impact of Annular Solar Eclipse of 15 January 2010 on the Atmospheric Boundary Layer Characteristics Over Thumba: A Case Study - D. Bala Subrahamanyam; T. J. Anurose; Mannil Mohan; M. Santosh; N. V. P. Kiran Kumar; S. Sijikumar (Pure and Applied Geophysics, 2012)

Soil warming alters nitrogen cycling in a New England forest: implications for ecosystem function and structure - S. M. Butler; J. M. Melillo; J. E. Johnson; J. Mohan; P. A. Steudler; H. Lux; E. Burrows; R. M. Smith; C. L. Vario; L. Scott; T. D. Hill; N. Aponte; et al. (Oecologia, 2012)

Assessment of drinking water quality using ICP-MS and microbiological methods in the Bholakpur area, Hyderabad, India - Rasheed M. Abdul; Lakshmi Mutnuri; Patil J. Dattatreya; Dayal A. Mohan (Environmental Monitoring and Assessment, 2012)

Vertical structure of sea-breeze circulation over Thumba (8.5°N, 76.9°E, India) in the winter months and a case study during W-ICARB field experiment - T. J. Anurose; D. Bala Subrahamanyam; C. B. S. Dutt; N. V. P. Kiran Kumar; Sherine Rachel John; Sandhya K. Nair; M. Santosh; Mannil Mohan; P. K. Kunhikrishnan; S. Sijikumar; S. S. Prijith (Meteorology and Atmospheric Physics, 2012)

Atmospheric Surface-Layer Response to the Annular Solar Eclipse of 15 January 2010 over Thiruvananthapuram, India - D. Bala Subrahamanyam; T. J. Anurose; Mannil Mohan; M. Santosh; N. V. P. Kiran Kumar; S. Sijikumar; S. S. Prijith; Marina Aloysius (Boundary-Layer Meteorology, 2011)

Image cytometric determination of nuclear and chromosomal DNA contents in Allium cepa L. - V. Rao Bandaru; Tavva S. S. Mohan Dev; P. V. Arjuna Rao; M. V. Subba Rao (The Nucleus, 2011)

Direct somatic embryogenesis and plantlet regeneration in oil palm - M. Jayanthi; N. Murali Mohan; P. K. Mandal (Journal of Plant Biochemistry and Biotechnology, 2011)

Impaired miR-146a expression links subclinical inflammation and insulin resistance in Type 2 diabetes - M. Balasubramanyam; S. Aravind; K. Gokulakrishnan; P. Prabu; C. Sathishkumar; H. Ranjani; V. Mohan (Molecular and Cellular Biochemistry, 2011)

Temporal changes in circulating levels of plasma interleukin-8 during peripartum period in Murrah buffaloes (Bubalus bubalis) under subtropical climate - Vijay Kumar; Parveen Kumar; Krishna Mohan; Mihir Sarkar; K. P. Suresh; M. S. Chauhan; B. S. Prakash (Tropical Animal Health and Production, 2011)

Archaean gold mineralization synchronous with late cratonization of the Western Dharwar Craton, India: 2.52 Ga U–Pb ages of hydrothermal monazite and xenotime in gold deposits - D. Srinivasa Sarma; Ian R. Fletcher; Birger Rasmussen; Neal J. McNaughton; M. Ram Mohan; David I. Groves (Mineralium Deposita, 2011)

Exploitation of the late flowering species Brassica oleracea L. for the improvement of earliness in B. napus L.: an untraditional approach - M. Habibur Rahman; Rick A. Bennett; Rong-Cai Yang; Berisso Kebede; Mohan R. Thiagarajah (Euphytica, 2011)

Estimating aquifer thickness using multiple pumping tests - Jean-Christophe Maréchal; Jean-Michel Vouillamoz; M. S. Mohan Kumar; Benoit Dewandel (Hydrogeology Journal, 2010)

Quantification of Mineral Elements of Rheum emodi Wallr. (Polygonaceae) - Pramod Singh; Jagmohan S. Negi; Mohan S. M. Rawat; Geeta Joshi nee Pant (Biological Trace Element Research, 2010)

Complete nucleotide sequence of cherry virus A (CVA) infecting sweet cherry in India - M. S. Noorani; P. Awasthi; Rahul Mohan Singh; Raja Ram; M. P. Sharma; S. R. Singh; N. Ahmed; V. Hallan; A. A. Zaidi (Archives of Virology, 2010)

Ostracoda as an aid in identifying 2004 tsunami sediments: a report from SE coast of India - S. M. Hussain; S. P. Mohan; M. P. Jonathan (Natural Hazards, 2010)

Boronated phosphonium salts containing arylboronic acid, closo-carborane, or nido-carborane: synthesis, X-ray diffraction, in vitro cytotoxicity, and cellular uptake - Daniel E. Morrison; Fatiah Issa; Mohan Bhadbhade; Ludwig Groebler; Paul K. Witting; Michael Kassiou; Peter J. Rutledge; Louis M. Rendina (JBIC Journal of Biological Inorganic Chemistry, 2010)

Land-cover change dynamics and coastal aquaculture development: a case study in the East Godavari delta, Andhra Pradesh, India using multi-temporal satellite data - K. Rajitha; C. K. Mukherjee; R. Vinu Chandran; M. M. Prakash Mohan (International Journal of Remote Sensing, 2010)

Clinical white spot disease status in Penaeus monodon during the middle of the culture period – its epidemiological significance - A K Sahoo; C V Mohan; K M Shankar; F Corsin; J F Turnbull; P C Thakur; N V Hao; K L Morgan; A P Padiyar (Journal of Fish Diseases, 2010)

A study on pre- and post-tsunami shallow deposits off SE coast of India from the 2004 Indian Ocean tsunami: a geochemical approach - S. Srinivasalu; M. P. Jonathan; N. Thangadurai; V. Ram-Mohan (Natural Hazards, 2010)

Management of Multipurpose Multireservoir Using Fuzzy Interactive Method - K. Deep; Krishna Pratap Singh; M. L. Kansal; C. Mohan (Water Resources Management, 2009)

Molecular mapping of rice blast resistance gene Pi-1(t) in the elite indica variety Samba mahsuri - M. Srinivas Prasad; B. Aruna Kanthi; S. M. Balachandran; M. Seshumadhav; K. Madhan Mohan; B. C. Viraktamath (World Journal of Microbiology and Biotechnology, 2009)

Structure-function-folding relationships and native energy landscape of dynein light chain protein: nuclear magnetic resonance insights - P. M. Krishna Mohan; Ramakrishna V. Hosur (Journal of Biosciences, 2009)

Relative Microalgal Concentration in Prydz Bay, East Antarctica during Late Austral Summer, 2006 - Rahul Mohan; Sunil Kumar Shukla; N. Anilkumar; M. Sudhakar; Satya Prakash; R. Ramesh (Algae, 2009)

Molecular convergence of hexosamine biosynthetic pathway and ER stress leading to insulin resistance in L6 skeletal muscle cells - V. Srinivasan; U. Tatu; V. Mohan; M. Balasubramanyam (Molecular and Cellular Biochemistry, 2009)

A case study of atmospheric boundary layer features during winter over a tropical inland station — Kharagpur (22.32°N, 87.32°E) - Denny P. Alappattu; P. K. Kunhikrishnan; Marina Aloysius; M. Mohan (Journal of Earth System Science, 2009)

A possible tradeoff between developmental rate and pathogen resistance in Drosophila melanogaster - Shampa Ghosh Modak; K. M. Satish; J. Mohan; Sutirth Dey; N. Raghavendra; Mallikarjun Shakarad; Amitabh Joshi (Journal of Genetics, 2009)

Decreased mass specific respiration under experimental warming is robust to the microbial biomass method employed - Mark A. Bradford; Matthew D. Wallenstein; Steven D. Allison; Kathleen K. Treseder; Serita D. Frey; Brian W. Watts; Christian A. Davies; Thomas R. Maddox; Jerry M. Melillo; Jacqueline E. Mohan; James F. Reynolds (Ecology Letters, 2009)
Hartley et al. question whether reduction in R mass , under experimental warming, arises because of the biomass method. We show the method they treat as independent yields the same result. We describe why the substrate‐depletion hypothesis may not solely explain observed responses, and urge caution in interpretation of the seasonal data.

Developmentally linked changes in proteases and protease inhibitors suggest a role for potato multicystatin in regulating protein content of potato tubers - Sarah M. Weeda; G. N. Mohan Kumar; N. Richard Knowles (Planta, 2009)

Nitrilase-catalysed conversion of acrylonitrile by free and immobilized cells of Streptomyces sp. - V. K. Nigam; A. K. Khandelwal; R. K. Gothwal; M. K. Mohan; B. Choudhury; A. S. Vidyarthi; P. Ghosh (Journal of Biosciences, 2009)

Kinetics of immune response to foot-and-mouth disease virus (type Asia 1) in experimental cattle - M. S. Mohan; M. R. Gajendragad; Subodh Kishore; S. Gopalakrishna; Nem Singh (Veterinary Research Communications, 2009)

Origin and characterisation of microparticles in an ice core from the Central Dronning Maud Land, East Antarctica - C. M. Laluraj; K. P. Krishnan; M. Thamban; R. Mohan; S. S. Naik; W. D’Souza; R. Ravindra; A. Chaturvedi (Environmental Monitoring and Assessment, 2009)

Estimation of forest biophysical variables from Indian Earth Observation Satellite Cartosat‐1 stereo data - M. M. Kimothi; S. Mohan; R. B. Singh; P. Soni; H. B. Vashistha; Ajai (International Journal of Remote Sensing, 2009)

Mapping of the chromosome 17 BMD QTL in the F2 male mice of MRL/MpJ × SJL/J - Hongrun Yu; Bouchra Edderkaoui; Alejandro Cortez; Heather M. Davidson; Jon E. Wergedal; David J. Baylink; Subburaman Mohan (Genetica, 2009)

Thermal adaptation of soil microbial respiration to elevated temperature - Mark A. Bradford; Christian A. Davies; Serita D. Frey; Thomas R. Maddox; Jerry M. Melillo; Jacqueline E. Mohan; James F. Reynolds; Kathleen K. Treseder; Matthew D. Wallenstein (Ecology Letters, 2008)
In the short‐term heterotrophic soil respiration is strongly and positively related to temperature. In the long‐term, its response to temperature is uncertain. One reason for this is because in field experiments increases in respiration due to warming are relatively short‐lived. The explanations proposed for this ephemeral response include depletion of fast‐cycling, soil carbon pools and thermal adaptation of microbial respiration. Using a > 15 year soil warming experiment in a mid‐latitude forest, we show that the apparent ‘acclimation’ of soil respiration at the ecosystem scale results from combined effects of reductions in soil carbon pools and microbial biomass, and thermal adaptation of microbial respiration. Mass‐specific respiration rates were lower when seasonal temperatures were higher, suggesting that rate reductions under experimental warming likely occurred through temperature‐induced changes in the microbial community. Our results imply that stimulatory effects of global temperature rise on soil respiration rates may be lower than currently predicted.

Screening of Chemical Penetration Enhancers for Transdermal Drug Delivery Using Electrical Resistance of Skin - Vijay Krishna Rachakonda; Krishna Mohan Yerramsetty; Sundararajan V. Madihally; Robert L. Robinson; Khaled A. M. Gasem (Pharmaceutical Research, 2008)

Interspecific cross of Brassica oleracea var. alboglabra and B. napus: effects of growth condition and silique age on the efficiency of hybrid production, and inheritance of erucic acid in the self-pollinated backcross generation - Rick A. Bennett; Mohan R. Thiagarajah; Jane R. King; M. Habibur Rahman (Euphytica, 2008)

Development of tomato hybrids resistant to tomato leaf curl virus disease in South India - K. S. Shankarappa; Sriharsha; K. T. Rangaswamy; D. S. Aswathanarayana; H. A. Prameela; R. S. Kulkarni; V. Muniyappa; A. Mohan Rao; M. N. Maruthi (Euphytica, 2008)

Comparative study of experimental Foot-and-Mouth Disease in cattle (Bos indicus) and buffaloes (Bubalis bubalus) - M. S. Mohan; M. R. Gajendragad; S. Gopalakrishna; Nem Singh (Veterinary Research Communications, 2008)

Watershed development in India. 1. Biophysical and societal impacts - Ian Calder; Ashvin Gosain; M. S. Rama Mohan Rao; Charles Batchelor; M. Snehalatha; Emma Bishop (Environment, Development and Sustainability, 2008)

Watershed development in India. 2. New approaches for managing externalities and meeting sustainability requirements - Ian Calder; Ashvin Gosain; M. S. Rama Mohan Rao; Charles Batchelor; James Garratt; Emma Bishop (Environment, Development and Sustainability, 2008)

A novel association of a polymorphism in the first intron of adiponectin gene with type 2 diabetes, obesity and hypoadiponectinemia in Asian Indians - Karani S. Vimaleswaran; Venkatesan Radha; Kandaswamy Ramya; Hunsur Narayan Sathish Babu; Nageshappa Savitha; Venkataramaiah Roopa; Dhar Monalisa; Raj Deepa; Saurabh Ghosh; Partha P. Majumder; M. R. Sathyanarayana Rao; Viswanathan Mohan (Human Genetics, 2008)

High doses of dietary zinc induce cytokines, chemokines, and apoptosis in reproductive tissues during regression - N. R. Sundaresan; D. Anish; K. V. H. Sastry; V. K. Saxena; K. Nagarajan; J. Subramani; M. D. M. Leo; N. Shit; J. Mohan; M. Saxena; K. A. Ahmed (Cell and Tissue Research, 2008)

Synergistic interaction between sublethal doses of Bacillus thuringiensis and Campoletis chlorideae in managing Helicoverpa armigera - M. Mohan; S. N. Sushil; J. C. Bhatt; G. T. Gujar; H. S. Gupta (BioControl, 2008)

Effect of Therapy on Serum Zinc and Copper in Primary Complex of Children - G. Mohan; S. Kulshreshtha; R. Dayal; M. Singh; P. Sharma (Biological Trace Element Research, 2007)

Time to death in the presence of E. coli: a mass-scale method for assaying pathogen resistance in Drosophila - N. Sharmila Bharathi; N. Archana; Anjana Badrinarayanan; K. M. Satish; J. Mohan; Amitabh Joshi (Journal of Genetics, 2007)

An algebraic targeting approach for effective utilization of biomass in combined heat and power systems through process integration - Tanya Mohan; Mahmoud M. El-Halwagi (Clean Technologies and Environmental Policy, 2007)

Mutant prion protein D202N associated with familial prion disease is retained in the endoplasmic reticulum and forms ‘curly’ intracellular aggregates - Y. Gu; S. Verghese; S. Bose; M. Mohan; N. Singh (Journal of Molecular Neuroscience, 2007)

Seasonal variation of pteropods from the Western Arabian Sea sediment trap - R. Mohan; K. Verma; L. P. Mergulhao; D. K. Sinha; S. Shanvas; M. V. S. Guptha (Geo-Marine Letters, 2006)

Coccolithophores from the central Arabian Sea: Sediment trap results - Lina P. Mergulhao; Rahul Mohan; V. S. N. Murty; M. V. S. Guptha; D. K. Sinha (Journal of Earth System Science, 2006)

Detecting and estimating segregation distortion and linkage between glufosinate tolerance and blackleg resistance in Brassica napus L. - Rong-Cai Yang; Mohan R. Thiagarajah; Vipan K. Bansal; Gary R. Stringam; M. Habibur Rahman (Euphytica, 2006)

An algebraic targeting approach for effective utilization of biomass in combined heat and power systems through process integration - Tanya Mohan; Mahmoud M. El-Halwagi (Clean Technologies and Environmental Policy, 2006)

Tolerance of Bt corn (MON 810) to maize stem borer, Chilo partellus (Lepidoptera: Pyralidae) - Ramkumar; K. C. Ravi; Farah Deeba; J. N. Nandi; K. S. Mohan; T. M. Manjunath (Plant Cell Reports, 2005)

A GIS based hydrogeomorphic approach for identification of site-specific artificial-recharge techniques in the Deccan Volcanic Province - M. N. Ravi Shankar; G. Mohan (Journal of Earth System Science, 2005)

Changes in the source and transport mechanism of terrigenous input to the Indian sector of Southern Ocean during the late Quaternary and its palaeoceanographic implications - M. Thamban; S. S. Naik; R. Mohan; A. Rajakumar; N. Basavaiah; Witty D’Souza; Sarita Kerkar; M. M. Subramaniam; M. Sudhakar; P. C. Pandey (Journal of Earth System Science, 2005)

Editorial - V. Mohan Kumar; M. Okawa (Sleep and Biological Rhythms, 2005)

Characterization of Insect Proteinases and Their Inhibition by Finger and Little Millet Inhibitors - S Sivakumar; M Mohan; B Thayumanavan (Journal of Plant Biochemistry and Biotechnology, 2005)

Tagging and mapping of a rice gall midge resistance gene, Gm8, and development of SCARs for use in marker-aided selection and gene pyramiding - A. Jain; R. Ariyadasa; A. Kumar; M. N. Srivastava; M. Mohan; S. Nair (Theoretical and Applied Genetics, 2004)

Use of sugarcane bagasse as an alternative low-cost support material during the rooting stage of apple micropropagation - R. Mohan; C. R. Soccol; M. Quoirin; A. Pandey (In Vitro Cellular & Developmental Biology - Plant, 2004)

Study of momentum transfers within a vegetation canopy - Mahendra Mohan; M. K. Tiwari (Journal of Earth System Science, 2004)

Curcumin-induced inhibition of cellular reactive oxygen species generation: Novel therapeutic implications - M. Balasubramanyam; A. Adaikala Koteswari; R. Sampath Kumar; S. Finny Monickaraj; J. Uma Maheswari; V. Mohan (Journal of Biosciences, 2003)

Induction of systemic resistance to Xanthomonas oryzae pv. oryzae by salicylic acid in Oryza sativa (L.) - R. Mohan Babu; A. Sajeena; A. Vijaya Samundeeswari; A. Sreedhar; P. Vidhyasekaran; K. Seetharaman; M. S. Reddy (Journal of Plant Diseases and Protection, 2003)

Stress and aberrant phenotypes in vitro culture - Siobhan M. Joyce; Alan C. Cassells; S. Mohan Jain (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)

Characterization of a phytotoxic glycoprotein produced byPhoma eupyrena — A pathogen on water lettuce - R. Mohan Babu; A. Sajeena; P. Vidhyasekaran; K. Seetharaman; M. S. Reddy (Phytoparasitica, 2003)

Host-pathogen interactions during apoptosis - Seyed E. Hasnain; Rasheeda Begum; K. V. A. Ramaiah; Sudhir Sahdev; E. M. Shajil; Tarvinder K. Taneja; Manjari Mohan; M. Athar; Nand K. Sah; M. Krishnaveni (Journal of Biosciences, 2003)

An Overview of the Land Surface Processes Experiment (Laspex) over a Semi-Arid Region of India - K. G. Vernekar; S. Sinha; L. K. Sadani; S. Sivaramakrishnan; S. S. Parasnis; Brij Mohan; S. Dharmaraj; M. N. Patil; J. S. Pillai; B. S. Murthy; S. B. Debaje; A. Bagavathsingh (Boundary-Layer Meteorology, 2003)

Detection of marine aerosols with IRS P4-Ocean Colour Monitor - Indrani Das; M. Mohan; K. Krishnamoorthy (Journal of Earth System Science, 2002)

Identification and mapping of an AFLP marker linked to Gm7, a gall midge resistance gene and its conversion to a SCAR marker for its utility in marker aided selection in rice - N. Sardesai; A. Kumar; K. Rajyashri; S. Nair; M. Mohan (Theoretical and Applied Genetics, 2002)

Comparison of ocean color chlorophyll algorithms for IRS-P4 OCM sensor usingin-situ data - Prakash Chauhan; M Mohan; S R Nayak; R R Navalgund (Journal of the Indian Society of Remote Sensing, 2002)

Effect of dietary vitamin C on the inflammatory response of mrigal, Cirrhinus mrigala (Hamilton), to Freund's complete adjuvant - K S Sobhana; C V Mohan; K M Shankar (Journal of Fish Diseases, 2002)

Orally active insulin mimics: where do we stand now? - M. Balasubramanyam; V. Mohan (Journal of Biosciences, 2001)

Carbon Stock, Afforestation and Acidic Deposition: An Analysis of Inter-Relation with Reference to Arid Areas - Sanjay Kumar; R. Datta; S. Sinha; T. Kojima; S. Katoh; M. Mohan (Water, Air, & Soil Pollution, 2001)

Somatic embryogenesis from leaf cultures of potato - T. JayaSree; U. Pavan; M. Ramesh; A.V. Rao; K. Jagan Mohan Reddy; A. Sadanandam (Plant Cell, Tissue and Organ Culture (PCTOC), 2001)

The complete primary structure of mouse 20S proteasomes - Laura A. Elenich; D. Nandi; A. Elizabeth Kent; T. Scott McCluskey; M. Cruz; Mohan N. Iyer; Elaine C. Woodward; Christopher W. Conn; Amber L. Ochoa; David B. Ginsburg; J. J. Monaco (Immunogenetics, 1999)

Resistance gene analogues from rice: cloning, sequencing and mapping - R. Mago; S. Nair; M. Mohan (Theoretical and Applied Genetics, 1999)

Downregulation of the urokinase-type plasminogen activator receptor through inhibition of translation by antisense oligonucleotide suppresses invasion of human glioblastoma cells - Pamarthi M. Mohan; Sajani S. Lakka; Sanjeeva Mohanam; Yoshiaki Kin; Raymond Sawaya; Anthanassios P. Kyritsis; Garth L. Nicolson; Jasti S. Rao (Clinical & Experimental Metastasis, 1999)

Morphological and molecular analysis of genetic stability in micropropagated Fragaria×Ananassa cv. pocahontas - Mohan B. Kumar; Reed E. Barker; Barbara M. Reed (In Vitro Cellular & Developmental Biology - Plant, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Invitro culturedSpodoptera frugiperda insect cells: Model for oxidative stress-induced apoptosis - Seyed E. Hasnain; Tarvinder K. Taneja; Nand K. Sah; Manjari Mohan; Niteen Pathak; Sudhir Sahdev; Mohammad Athar; Satish M. Totey; Rasheedunnisa Begum (Journal of Biosciences, 1999)

Angiotensin II type 1 receptor-modulated signaling pathways in neurons - Elaine M. Richards; Mohan K. Raizada; Craig H. Gelband; Colin Sumners (Molecular Neurobiology, 1999)

Isolation and FISH mapping of Yeast Artificial Chromosomes (YACs) encompassing an allele of the Gm2 gene for gall midge resistance in rice - K. R. Rajyashri; S. Nair; N. Ohmido; K. Fukui; N. Kurata; T. Sasaki; M. Mohan (Theoretical and Applied Genetics, 1998)

Effect of short term vitamin E supplementation on lipid peroxidation in acute myocardial infarction - A. P. Jain; A. Mohan; O. P. Gupta; U. N. Jajoo; S. P. Kalantri; L. M. Srivastava (Indian Journal of Clinical Biochemistry, 1998)

Plant regeneration in pigeonpea [ Cajanus cajan (L.) Millsp.] by organogenesis - M. L. Mohan; K. V. Krishnamurthy (Plant Cell Reports, 1998)

Molecular mapping of a resistance-specific PCR-based marker linked to a gall midge resistance gene (Gm4t) in rice - M. Mohan; P. V. Sathyanarayanan; A. Kumar; M. N. Srivastava; S. Nair (Theoretical and Applied Genetics, 1997)

Productivity, soil fertility and soil erosion under cassava based agroforestry systems - S. P. Ghosh; B. Mohan Kumar; S. Kabeerathumma; G. M. Nair (Agroforestry Systems, 1989)

Wild mouse retrovirus-induced neurogenic paralysis in laboratory mice - B. K. Pal; S. Mohan; Rosemarie Nimo; M. B. Gardner (Archives of Virology, 1983)

l-Threonine dehydratase activity of axenically grown Hartmannella culbertsoni - M. K. Raizada; V. K. Mohan Rao (Archives of Microbiology, 1972)